Microcrystalline glass and microcrystalline glass article having spinel crystalline phase
Patent Information
- Application Number
- CN202510269173.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-04-27
AI Technical Summary
Ti3+离子容易在所形成的晶相中稳定存在,导致微晶玻璃着色(棕黄色),从而降低微晶玻璃在可见光区的透过率
[0102]本发明的有益效果是:通过合理的组分设计,本发明获得的具有尖晶石晶相的微晶玻璃或具有尖晶石晶相的微晶玻璃制品具有优异的光透过率和机械性能。
Smart Images

Figure BDA0005302150800000291 
Figure BDA0005302150800000321 
Figure BDA0005302150800000322
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202310470742.X, application date April 27, 2023, entitled "Microcrystalline Glass Having Spinel Phase and Microcrystalline Glass Articles". Technical Field
[0002] This invention relates to a glass-ceramic, and more particularly to a glass-ceramic having a spinel crystal phase and glass-ceramic articles thereof. Background Technology
[0003] Glass-ceramics are polycrystalline solid materials formed by the controlled crystallization of specific glass components. They combine the structural characteristics and properties of both glass and ceramics, and are a new type of inorganic non-metallic material that is under development and has broad application prospects. Glass-ceramics possess excellent properties such as high mechanical strength, low coefficient of thermal expansion, good corrosion resistance, high hardness, and good wear resistance, and can be applied in fields such as electronics, machinery, aerospace, and biomedicine.
[0004] Microcrystalline glass with a spinel crystal phase is used in display devices or electronic devices, especially in the front and back covers of portable electronic devices (such as mobile phones, watches, and tablets), where it has significant advantages over materials such as ceramics and sapphire. Microcrystalline glass with a spinel crystal phase has a smooth surface, a completely dense and uniform structure, is not easily contaminated, and its manufacturing process is relatively simple, with high production capacity and lower cost. Compared with high-alumina glass, microcrystalline glass with a spinel crystal phase exhibits higher mechanical strength, hardness, impact resistance, thermal conductivity, and superior thermal and chemical stability.
[0005] In existing technologies, TiO2 is used as a nucleating agent to prepare microcrystalline glass with a spinel crystal phase. However, the Ti element introduced by TiO2 easily undergoes a valence change in the glass, forming Ti... 3+ Ions. Ti 3+ Ions tend to remain stable within the formed crystalline phase, causing the glass-ceramic to become brownish-yellow, thus reducing its transmittance in the visible light region. Furthermore, spinel has a high refractive index (1.83), which differs significantly from the refractive index of the matrix glass; the precipitation of the spinel crystalline phase also reduces the transmittance of the glass-ceramic in the visible light region. These factors limit the application of glass-ceramics with spinel crystalline phases in electronic and display devices. Therefore, improving the transmittance of glass-ceramics with spinel crystalline phases is a problem that urgently needs to be solved. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a microcrystalline glass and microcrystalline glass products with spinel crystal phase having excellent light transmittance and mechanical properties.
[0007] The technical solution adopted by this invention to solve the technical problem is:
[0008] (1). Microcrystalline glass products with spinel crystal phase, whose composition is expressed as a percentage by weight, contains: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%, of which Li2O / TiO2 is 0.2-4.5.
[0009] (2). The microcrystalline glass product with spinel phase according to (1) further comprises, by weight percentage: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifying agent: 0-2%.
[0010] (3) Microcrystalline glass products with spinel crystal phase, whose components contain SiO2, Al2O3, Li2O, ZnO and TiO2, and whose transmittance of light at a wavelength of 550nm is above 87.0% for microcrystalline glass products with a thickness of less than 1mm.
[0011] (4). A microcrystalline glass product having a spinel crystal phase, the composition of which contains SiO2, Al2O3, Li2O, ZnO and TiO2, wherein the impact resistance of the microcrystalline glass product is above 1200mm.
[0012] (5) A microcrystalline glass product having a spinel crystal phase, wherein the composition contains SiO2, Al2O3 and ZnO, and the compressive strength of the microcrystalline glass product is above 400N.
[0013] (6) Microcrystalline glass products with spinel crystal phase, the haze of microcrystalline glass products with a thickness of less than 1 mm is less than 0.3%.
[0014] (7) A microcrystalline glass product having a spinel crystal phase, wherein the drop ball test height of the microcrystalline glass product is 1000 mm or more.
[0015] (8) Microcrystalline glass products with spinel crystal phase, whose composition contains SiO2, Al2O3, Li2O, ZnO and TiO2, and whose average optical |B| value of 400-800nm is less than 1.0 for microcrystalline glass products with a thickness of less than 1mm.
[0016] (9) A microcrystalline glass product having a spinel crystal phase, wherein the composition contains SiO2, Al2O3, Li2O, ZnO and TiO2, and the ion exchange layer depth of the microcrystalline glass product is 75 μm or more.
[0017] (10) A microcrystalline glass product having a spinel crystal phase, wherein the composition contains SiO2, Al2O3 and Li2O, and the surface stress of the microcrystalline glass product is above 200MPa.
[0018] (11). A microcrystalline glass product having a spinel crystal phase, wherein the composition contains SiO2, Al2O3, ZnO and TiO2, and the grain size of the microcrystalline glass product is less than 60 nm.
[0019] (12). Microcrystalline glass products with spinel crystal phase, the transmittance of light at a wavelength of 550nm is above 87.0% for microcrystalline glass products with a thickness of less than 1mm.
[0020] (13) A microcrystalline glass product having a spinel crystal phase, the composition of which contains SiO2, Al2O3 and ZnO, wherein the Vickers hardness of the microcrystalline glass product is 650 kgf / mm. 2 above.
[0021] (14). The microcrystalline glass article having a spinel phase according to any one of (3) to (13) contains, by weight percentage: SiO2: 40-55%; and / or Al2O3+ZnO: 26-45%; and / or Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or TiO2: 0.5-7%; and / or P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifying agent: 0-2%.
[0022] (15) Microcrystalline glass products with spinel crystal phase, the composition of which is expressed as a weight percentage as follows: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%; P2O5+ZrO2: 0-8%; Na2O: 0-6%; B2O3: 0-4%; K2O: 0-3%; CaO+BaO+SrO: 0-5%; Y2O3: 0-6%; clarifying agent: 0-2%.
[0023] (16). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: Li2O / TiO2 is 0.2 to 4.5, preferably Li2O / TiO2 is 0.5 to 3.5, more preferably Li2O / TiO2 is 0.7 to 2.5, and even more preferably Li2O / TiO2 is 0.75 to 1.5.
[0024] (17). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: Al2O3 / ZnO is 1.0 to 3.0, preferably Al2O3 / ZnO is 1.2 to 2.8, more preferably Al2O3 / ZnO is 1.25 to 2.5, and even more preferably Al2O3 / ZnO is 1.5 to 2.3.
[0025] (18). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: SiO2 / Al2O3 is 1.5 to 3.2, preferably SiO2 / Al2O3 is 1.7 to 3.0, more preferably SiO2 / Al2O3 is 1.8 to 2.8, and even more preferably SiO2 / Al2O3 is 2.0 to 2.5.
[0026] (19). The microcrystalline glass article having spinel phase according to any one of (1) to (15) has the following composition expressed as a weight percentage: (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, and even more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9.
[0027] (20). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: (Li2O+MgO) / TiO2 is 0.3 to 8.0, preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, more preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and even more preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5.
[0028] (21). The microcrystalline glass product with spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and even more preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5.
[0029] (22). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and even more preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0.
[0030] (23). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the components are expressed as weight percentages, wherein: P2O5 / ZrO2 is 0.1 to 5.0, preferably P2O5 / ZrO2 is 0.2 to 3.0, more preferably P2O5 / ZrO2 is 0.5 to 2.0, and even more preferably P2O5 / ZrO2 is 0.6 to 1.5.
[0031] (24). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein: (SiO2+Na2O) / ZnO is 2.2 to 6.2, preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, more preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and even more preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0.
[0032] (25). The microcrystalline glass article having spinel phase according to any one of (1) to (15), wherein the composition is expressed as a weight percentage, wherein (Na2O+K2O) / ZnO is 0.8 or less, preferably (Na2O+K2O) / ZnO is 0.6 or less, more preferably (Na2O+K2O) / ZnO is 0.4 or less, and even more preferably (Na2O+K2O) / ZnO is 0.2 or less.
[0033] (26) The microcrystalline glass article having a spinel phase according to any one of (1) to (15), wherein the composition, expressed as a percentage by weight, contains: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2 ~5%; and / or P2O5+ZrO2: 0.1-7%, preferably P2O5+ZrO2: 0.5-5%; and / or Na2O: 0-4%, preferably Na2O: 0-2%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or Y2O3: 0-4%, preferably Y2O3: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%.
[0034] (27). The microcrystalline glass article having a spinel phase according to any one of (1) to (15) contains, by weight percentage: Al2O3: 15-30%, preferably Al2O3: 18-25%, more preferably Al2O3: 20-23%; and / or ZnO: 9-20%, preferably ZnO: 11-18%, more preferably ZnO: 12-16%; and / or P2O5: 0-5%, preferably P2O5: 0.5-4%, more preferably P2O5: 1-3%; and / or ZrO2: 0-5%, preferably ZrO2: 0.5-4%, more preferably ZrO2: 1-3%.
[0035] (28). The microcrystalline glass article having a spinel crystal phase according to any one of (1) to (15), wherein the spinel crystal phase accounts for 20 to 60% of the weight percentage of the microcrystalline glass article, preferably 25 to 50% of the weight percentage of the microcrystalline glass article, more preferably 25 to 45% of the weight percentage of the spinel crystal phase of the microcrystalline glass article, and even more preferably 30 to 45% of the weight percentage of the spinel crystal phase of the microcrystalline glass article.
[0036] (29). A microcrystalline glass article having a spinel crystal phase according to any one of (1) to (15), wherein the microcrystalline glass article having a spinel crystal phase contains a quartz crystal phase, preferably the quartz crystal phase accounts for 20% or less of the weight percentage of the microcrystalline glass article, more preferably the quartz crystal phase accounts for 10% or less of the weight percentage of the microcrystalline glass article, even more preferably the quartz crystal phase accounts for 5% or less of the weight percentage of the microcrystalline glass article, and even more preferably the microcrystalline glass article having a spinel crystal phase does not contain a quartz crystal phase.
[0037] (30) The microcrystalline glass article having a spinel phase according to any one of (1) to (14), wherein the composition, expressed as a weight percentage, contains: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2 %, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%, further preferably not containing La2O3, and / or not containing Gd2O3, and / or not containing Yb2O3, and / or not containing Nb2O5, and / or not containing WO3, and / or not containing Bi2O3, and / or not containing Ta2O5, and / or not containing TeO2.
[0038] (31) A microcrystalline glass article having a spinel crystal phase according to any one of (1) to (15), wherein the grain size of the microcrystalline glass article is 60 nm or less, preferably 45 nm or less, more preferably 10 to 30 nm; and / or the ion exchange layer depth is 75 μm or more, preferably 80 to 150 μm, more preferably 100 to 125 μm; and / or the surface stress is 200 MPa or more, preferably 250 to 400 MPa, more preferably 300 to 400 MPa; and / or the drop ball test height is 1000 mm or more, preferably 1200 mm or more, more preferably 1500 mm or more; and / or the drop resistance is 1200 mm or more, preferably 1300 mm or more, more preferably 1400 mm or more; and / or the fracture toughness is 1.0 MPa·m. 1 / 2 The above is preferably 1.2 MPa·m 1 / 2 The above, more preferably 1.2 to 1.6 MPa·m 1 / 2 ; and / or a four-point bending strength of 500 MPa or more, preferably 600 MPa or more, more preferably 700 to 1000 MPa; and / or a compressive strength of 400 N or more, preferably 400 to 550 N, more preferably 450 to 550 N; and / or a Vickers hardness of 650 kgf / mm 2 The preferred value is 660 kgf / mm².2 The above, more preferably 680–750 kgf / mm 2 .
[0039] (32). The microcrystalline glass article having spinel crystal phase according to any one of (1) to (15), wherein the haze of the microcrystalline glass article with a thickness of 1 mm or less is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%; and / or the average light transmittance at a wavelength of 400 to 800 nm is 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more; and / or the light transmittance at a wavelength of 550 nm is 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more; and / or the average light |B| value at 400 to 800 nm is 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6.
[0040] (33). The microcrystalline glass product with spinel crystal phase according to (32) has a thickness of 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0041] (34). The microcrystalline glass article having a spinel phase according to any one of (1) to (14) contains, by weight percentage: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
[0042] (35). The microcrystalline glass article having a spinel phase according to any one of (1) to (14), wherein the composition, expressed as a percentage by weight, contains: NiO: 0.1-4%; and / or Ni2O3: 0.1-4%; and / or CoO: 0.05-2%; and / or Co2O3: 0.05-2%; and / or Fe2O3: 0.2-7%; and / or MnO2: 0.1-4%; and / or Er2O3: 0.4-8%; and / or Nd2O3: 0.4-8%; and / or Cu2O: 0.5-4%; and / or Pr2O3: 0.4-8%; and / or CeO2: 0.5-4%.
[0043] (36). The microcrystalline glass article having a spinel phase according to any one of (1) to (14) contains, by weight percentage: NiO: 0.1-3%; and / or Ni2O3: 0.1-3%; and / or CoO: 0.05-1.8%; and / or Co2O3: 0.05-1.8%; and / or Fe2O3: 0.2-5%; and / or MnO2: 0.1-3%; and / or Er2O3: 0.4-6%; and / or Nd2O3: 0.4-6%; and / or Cu2O: 0.5-3%; and / or Pr2O3: 0.4-6%; and / or CeO2: 0.5-3%.
[0044] (37). The microcrystalline glass article having spinel phase according to any one of (1) to (14) contains, by weight percentage: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0045] (38). The microcrystalline glass article having spinel phase according to any one of (1) to (14) contains, by weight percentage: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0046] (39). The microcrystalline glass article having spinel phase according to any one of (1) to (14) contains, by weight percentage: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0047] (40). The microcrystalline glass article having a spinel phase according to any one of (1) to (14) contains, by weight percentage: Fe2O3: 0.2-5%, CoO: 0.05-0.3%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%; or Fe2O3: 0.2-5%, CoO: 0.05-0.3%, NiO: 0.1-1%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%, NiO: 0.1-1%.
[0048] (41). The microcrystalline glass article having a spinel phase according to any one of (1) to (14) contains, by weight percentage: Pr2O3: 0.4 to 6%; or Fe2O3: 0.2 to 5%; or MnO2: 0.1 to 3%; or Er2O3: 0.4 to 6%; or Nd2O3: 0.4 to 6%.
[0049] (42). The microcrystalline glass article having spinel phase according to any one of (1) to (14) contains, by weight percentage: Er2O3: 0.4 to 6%, Nd2O3: 0.4 to 4%, MnO2: 0.1 to 2%.
[0050] (43). Microcrystalline glass with spinel phase, the composition of which is expressed as weight percentage as follows: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%, of which Li2O / TiO2 is 0.2-4.5.
[0051] (44). The microcrystalline glass with spinel phase according to (43) further comprises, by weight percentage: P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifying agent: 0-2%.
[0052] (45) Microcrystalline glass with spinel phase, the composition of which contains SiO2, Al2O3, Li2O, ZnO and TiO2, has a light transmittance of more than 87.0% at a wavelength of 550nm for a thickness of less than 1mm.
[0053] (46). A glass-ceramic having a spinel phase, wherein the grain size of the glass-ceramic is less than 60 nm.
[0054] (47). Microcrystalline glass with spinel crystal phase, the composition of which contains SiO2, Al2O3, Li2O, ZnO and TiO2, and the haze of microcrystalline glass with a thickness of less than 1 mm is less than 0.3%.
[0055] (48). A microcrystalline glass having a spinel phase, the composition of which contains SiO2, Al2O3, ZnO and TiO2, wherein the Young's modulus of the microcrystalline glass is 80 to 110 GPa.
[0056] (49). Microcrystalline glass with spinel phase, containing SiO2, Al2O3, Li2O and ZnO in its composition, and the average optical |B| value of microcrystalline glass with a thickness of less than 1 mm at 400-800 nm is less than 1.0.
[0057] (50) Microcrystalline glass with spinel phase, containing SiO2, Al2O3 and ZnO, with an average light transmittance of more than 87.0% at wavelengths of 400 to 800 nm for a thickness of less than 1 mm.
[0058] (51). The microcrystalline glass having a spinel phase according to any one of (45) to (50), wherein the composition, expressed as a percentage by weight, contains: SiO2: 40-55%; and / or Al2O3+ZnO: 26-45%; and / or Li2O: 0.1-6%; and / or MgO: 0.1-6%; and / or TiO2: 0.5-7%; and / or P2O5+ZrO2: 0-8%; and / or Na2O: 0-6%; and / or B2O3: 0-4%; and / or K2O: 0-3%; and / or CaO+BaO+SrO: 0-5%; and / or Y2O3: 0-6%; and / or clarifying agent: 0-2%.
[0059] (52). Microcrystalline glass with spinel phase, the composition of which is expressed as a weight percentage as follows: SiO2: 40-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%; MgO: 0.1-6%; TiO2: 0.5-7%; P2O5+ZrO2: 0-8%; Na2O: 0-6%; B2O3: 0-4%; K2O: 0-3%; CaO+BaO+SrO: 0-5%; Y2O3: 0-6%; clarifier: 0-2%.
[0060] (53). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: Li2O / TiO2 is 0.2 to 4.5, preferably Li2O / TiO2 is 0.5 to 3.5, more preferably Li2O / TiO2 is 0.7 to 2.5, and even more preferably Li2O / TiO2 is 0.75 to 1.5.
[0061] (54). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: Al2O3 / ZnO is 1.0 to 3.0, preferably Al2O3 / ZnO is 1.2 to 2.8, more preferably Al2O3 / ZnO is 1.25 to 2.5, and even more preferably Al2O3 / ZnO is 1.5 to 2.3.
[0062] (55). The microcrystalline glass with spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: SiO2 / Al2O3 is 1.5 to 3.2, preferably SiO2 / Al2O3 is 1.7 to 3.0, more preferably SiO2 / Al2O3 is 1.8 to 2.8, and even more preferably SiO2 / Al2O3 is 2.0 to 2.5.
[0063] (56). The microcrystalline glass with spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, preferably (TiO2+ZnO) / Al2O3 is 0.5 to 1.2, more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 1.0, and even more preferably (TiO2+ZnO) / Al2O3 is 0.6 to 0.9.
[0064] (57). The microcrystalline glass with spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein (Li2O+MgO) / TiO2 is 0.3 to 8.0, preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, more preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and even more preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5.
[0065] (58). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: Al2O3 / (MgO+TiO2) is 1.3 to 10.0, preferably Al2O3 / (MgO+TiO2) is 1.5 to 8.0, more preferably Al2O3 / (MgO+TiO2) is 2.5 to 6.5, and even more preferably Al2O3 / (MgO+TiO2) is 3.0 to 5.5.
[0066] (59). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, more preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and even more preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0.
[0067] (60). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein: P2O5 / ZrO2 is 0.1 to 5.0, preferably P2O5 / ZrO2 is 0.2 to 3.0, more preferably P2O5 / ZrO2 is 0.5 to 2.0, and even more preferably P2O5 / ZrO2 is 0.6 to 1.5.
[0068] (61). The microcrystalline glass with spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein (SiO2+Na2O) / ZnO is 2.2 to 6.2, preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, more preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and even more preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0.
[0069] (62). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition is expressed as a weight percentage, wherein (Na2O+K2O) / ZnO is 0.8 or less, preferably (Na2O+K2O) / ZnO is 0.6 or less, more preferably (Na2O+K2O) / ZnO is 0.4 or less, and even more preferably (Na2O+K2O) / ZnO is 0.2 or less.
[0070] (63). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition, expressed in weight percentage, contains: SiO2: 45-53%, preferably SiO2: 48-52%; and / or Al2O3+ZnO: 30-42%, preferably Al2O3+ZnO: 32-42%, more preferably Al2O3+ZnO: 35-40%; and / or Li2O: 1-5%, preferably Li2O: 2-4%; and / or MgO: 1-5%, preferably MgO: 2-4%; and / or TiO2: 1-6%, preferably TiO2: 2-6%. 5%; and / or P2O5+ZrO2: 0.1-7%, preferably P2O5+ZrO2: 0.5-5%; and / or Na2O: 0-4%, preferably Na2O: 0-2%; and / or B2O3: 0-2%, preferably B2O3: 0-1%; and / or K2O: 0-2%, preferably K2O: 0-1%; and / or CaO+BaO+SrO: 0-4%, preferably CaO+BaO+SrO: 0-2%; and / or Y2O3: 0-4%, preferably Y2O3: 0-2%; and / or clarifying agent: 0-1%, preferably clarifying agent: 0-0.5%.
[0071] (64). The microcrystalline glass having a spinel phase according to any one of (43) to (52), wherein the composition, expressed in weight percentage, contains: Al2O3: 15-30%, preferably Al2O3: 18-25%, more preferably Al2O3: 20-23%; and / or ZnO: 9-20%, preferably ZnO: 11-18%, more preferably ZnO: 12-16%; and / or P2O5: 0-5%, preferably P2O5: 0.5-4%, more preferably P2O5: 1-3%; and / or ZrO2: 0-5%, preferably ZrO2: 0.5-4%, more preferably ZrO2: 1-3%.
[0072] (65). The glass-ceramic having a spinel phase according to any one of (43) to (52), wherein the spinel phase accounts for 20 to 60% of the weight of the glass-ceramic, preferably 25 to 50% of the weight of the glass-ceramic, more preferably 25 to 45% of the weight of the glass-ceramic, and even more preferably 30 to 45% of the weight of the glass-ceramic.
[0073] (66). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the microcrystalline glass having a spinel crystal phase contains a quartz crystal phase, preferably the quartz crystal phase accounts for 20% or less of the weight percentage of the microcrystalline glass, more preferably the quartz crystal phase accounts for 10% or less of the weight percentage of the microcrystalline glass, even more preferably the quartz crystal phase accounts for 5% or less of the weight percentage of the microcrystalline glass, and even more preferably the microcrystalline glass having a spinel crystal phase does not contain a quartz crystal phase.
[0074] (67) The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a weight percentage, contains: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-5%, preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0-2 %, more preferably La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%, further preferably not containing La2O3, and / or not containing Gd2O3, and / or not containing Yb2O3, and / or not containing Nb2O5, and / or not containing WO3, and / or not containing Bi2O3, and / or not containing Ta2O5, and / or not containing TeO2.
[0075] (68) A glass-ceramic having a spinel phase according to any one of (43) to (52), wherein the grain size of the glass-ceramic is less than 60 nm, preferably less than 45 nm, more preferably 10 to 30 nm; and / or the Young's modulus is 80 to 110 GPa, preferably 85 to 105 GPa, more preferably 90 to 105 GPa; and / or the Vickers hardness is 550 kgf / mm. 2 The preferred value is 580 kgf / mm². 2 The above, more preferably 600-650 kgf / mm 2 .
[0076] (69). The microcrystalline glass having a spinel crystal phase according to any one of (43) to (52), wherein the haze of the microcrystalline glass with a thickness of 1 mm or less is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%; and / or the average light transmittance at a wavelength of 400 to 800 nm is 87.0% or more, preferably 88.5% or more, more preferably 89.5% or more; and / or the light transmittance at a wavelength of 550 nm is 87.0% or more, preferably 88.0% or more, more preferably 89.0% or more; and / or the average light |B| value at 400 to 800 nm is 1.0 or less, preferably 0.8 or less, more preferably 0.3 to 0.6.
[0077] (70). The microcrystalline glass with spinel phase according to (69) has a thickness of 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0078] (71). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.
[0079] (72). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: NiO: 0.1-4%; and / or Ni2O3: 0.1-4%; and / or CoO: 0.05-2%; and / or Co2O3: 0.05-2%; and / or Fe2O3: 0.2-7%; and / or MnO2: 0.1-4%; and / or Er2O3: 0.4-8%; and / or Nd2O3: 0.4-8%; and / or Cu2O: 0.5-4%; and / or Pr2O3: 0.4-8%; and / or CeO2: 0.5-4%.
[0080] (73). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: NiO: 0.1-3%; and / or Ni2O3: 0.1-3%; and / or CoO: 0.05-1.8%; and / or Co2O3: 0.05-1.8%; and / or Fe2O3: 0.2-5%; and / or MnO2: 0.1-3%; and / or Er2O3: 0.4-6%; and / or Nd2O3: 0.4-6%; and / or Cu2O: 0.5-3%; and / or Pr2O3: 0.4-6%; and / or CeO2: 0.5-3%.
[0081] (74). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: NiO: 0.1 to 3%; and / or Ni2O3: 0.1 to 3%.
[0082] (75). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: CoO: 0.05 to 1.8%; and / or Co2O3: 0.05 to 1.8%.
[0083] (76). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: Cu2O: 0.5 to 3%; and / or CeO2: 0.5 to 3%.
[0084] (77). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: Fe2O3: 0.2-5%, CoO: 0.05-0.3%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%; or Fe2O3: 0.2-5%, CoO: 0.05-0.3%, NiO: 0.1-1%; or Fe2O3: 0.2-5%, Co2O3: 0.05-0.3%, NiO: 0.1-1%.
[0085] (78). The microcrystalline glass having a spinel phase according to any one of (43) to (51), wherein the composition, expressed as a percentage by weight, contains: Pr2O3: 0.4-6%; or Fe2O3: 0.2-5%; or MnO2: 0.1-3%; or Er2O3: 0.4-6%; or Nd2O3: 0.4-6%.
[0086] (79). The microcrystalline glass with spinel phase according to any one of (43) to (51) contains, by weight percentage: Er2O3: 0.4 to 6%, Nd2O3: 0.4 to 4%, MnO2: 0.1 to 2%.
[0087] (80). A glass cover containing a microcrystalline glass article having a spinel crystal phase as described in any one of (1) to (42), and / or a microcrystalline glass having a spinel crystal phase as described in any one of (43) to (79).
[0088] (81). Glass components, comprising microcrystalline glass articles having a spinel crystal phase as described in any of (1) to (42), and / or microcrystalline glass having a spinel crystal phase as described in any of (43) to (79).
[0089] (82). Electronic device comprising a microcrystalline glass article having a spinel crystal phase as described in any of (1) to (42), and / or a microcrystalline glass having a spinel crystal phase as described in any of (43) to (79), and / or a glass cover plate as described in (80), and / or a glass component as described in (81).
[0090] (83). A display device comprising a microcrystalline glass article having a spinel crystal phase as described in any of (1) to (42), and / or a microcrystalline glass having a spinel crystal phase as described in any of (43) to (79), and / or a glass cover plate as described in (80), and / or a glass component as described in (81).
[0091] (84). A method for manufacturing a microcrystalline glass article having a spinel crystal phase according to any one of (1) to (42), the method comprising the following steps: forming a matrix glass, forming a microcrystalline glass having a spinel crystal phase by crystallization process of the matrix glass, and forming a microcrystalline glass article having a spinel crystal phase by chemical strengthening process of the microcrystalline glass having a spinel crystal phase.
[0092] (85). According to the manufacturing method of the microcrystalline glass product with spinel phase described in (84), the formation of the matrix glass includes the following steps: mixing the raw materials evenly according to the component ratio, then placing them in a crucible, melting them in an electric furnace or gas furnace at a temperature range of 1350 to 1550°C for 5 to 24 hours, preferably at a melting temperature of 1450 to 1550°C, and then obtaining the matrix glass after clarification, homogenization, shaping and annealing, wherein the clarification temperature is greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is 450 to 600°C.
[0093] (86). According to the manufacturing method of the microcrystalline glass product with spinel crystal phase described in (84), the crystallization process includes the following steps: heating to a specified crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down. The crystallization treatment temperature is 600-800°C, preferably 650-750°C, and the holding time at the crystallization treatment temperature is 1-10 hours, preferably 3-6 hours.
[0094] (87). The method for manufacturing a microcrystalline glass product having a spinel crystal phase according to (84) includes the following steps: performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature.
[0095] (88). The method for manufacturing a microcrystalline glass product having a spinel crystal phase according to (87) includes the following crystallization process: a first temperature of 600-700°C, a second temperature greater than 700°C but less than or equal to 800°C, a holding time of 1-6 hours at the first temperature, and a holding time of 2-5 hours at the second temperature.
[0096] (89). According to the manufacturing method of the microcrystalline glass with spinel phase described in (84), the chemical strengthening process includes: immersing the microcrystalline glass with spinel phase in a salt bath of molten Na salt at 350-470°C for 1-36 hours, preferably at a temperature range of 400-460°C, and preferably for a time range of 2-15 hours; and / or immersing the microcrystalline glass with spinel phase in a mixed salt bath of molten K salt and Na salt at 360-450°C for 1-36 hours, preferably for a time range of 2-24 hours.
[0097] (90).(43)~(79) A method for manufacturing a microcrystalline glass having a spinel crystal phase, the method comprising the following steps: forming a matrix glass, and then forming a microcrystalline glass having a spinel crystal phase by crystallization process of the matrix glass.
[0098] (91). According to the manufacturing method of microcrystalline glass with spinel phase described in (90), the formation of matrix glass includes the following steps: mixing raw materials evenly according to the component ratio, then placing them in a crucible, melting them in an electric furnace or gas furnace at a temperature range of 1350-1550°C for 5-24 hours, preferably at a melting temperature of 1450-1550°C, and then obtaining matrix glass after clarification, homogenization, shaping and annealing, wherein the clarification temperature is greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is 450-600°C.
[0099] (92). According to the method for manufacturing microcrystalline glass with spinel phase as described in (90), the crystallization process includes the following steps: heating to a specified crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down. The crystallization treatment temperature is 600-800°C, preferably 650-750°C, and the holding time at the crystallization treatment temperature is 1-10 hours, preferably 3-6 hours.
[0100] (93). According to the manufacturing method of the microcrystalline glass product having spinel crystal phase as described in (90), the crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature.
[0101] (94). The method for manufacturing a microcrystalline glass product with spinel crystal phase according to (93) includes the following crystallization process: a first temperature of 600-700°C, a second temperature of greater than 700°C but less than or equal to 800°C, a holding time of 1-6 hours at the first temperature, and a holding time of 2-5 hours at the second temperature.
[0102] The beneficial effects of the present invention are: through reasonable component design, the microcrystalline glass with spinel crystal phase or the microcrystalline glass product with spinel crystal phase obtained by the present invention has excellent light transmittance and mechanical properties. Detailed Implementation
[0103] The microcrystalline glass with a spinel crystal phase and the microcrystalline glass articles of the present invention are materials having a crystalline phase (sometimes also referred to as crystal) and a glassy phase. The crystalline phase of the microcrystalline glass and the microcrystalline glass articles can be identified by the peak angle appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.
[0104] Through repeated experiments and research, the inventors of this invention, by specifying the content and proportion of specific components constituting microcrystalline glass with a spinel crystal phase and microcrystalline glass articles with a spinel crystal phase, and by ensuring that these components contain specific crystal phases, obtained the microcrystalline glass with a spinel crystal phase or microcrystalline glass articles with a spinel crystal phase of this invention. In this invention, the microcrystalline glass with a spinel crystal phase is sometimes simply referred to as microcrystalline glass, and the microcrystalline glass articles with a spinel crystal phase is sometimes simply referred to as microcrystalline glass articles.
[0105] The scope of each component (ingredient) of the matrix glass, microcrystalline glass, and microcrystalline glass articles of the present invention will be described below. In this specification, unless otherwise specified, the content of each component is expressed as a weight percentage (wt%) relative to the total amount of the matrix glass, microcrystalline glass, or microcrystalline glass article as a component of oxides. Here, "composition converted to oxides" means that when oxides, complex salts, and hydroxides used as raw materials for the matrix glass, microcrystalline glass, or microcrystalline glass articles of the present invention decompose and transform into oxides upon melting, the total amount of such oxides is taken as 100%. Furthermore, in this specification, when referred to simply as "glass," it refers to the matrix glass before crystallization (i.e., crystallization process treatment); after crystallization (i.e., crystallization process treatment), it is referred to as microcrystalline glass; and microcrystalline glass articles refer to products obtained by chemically strengthening microcrystalline glass.
[0106] Unless otherwise specified in the specific context, the numerical ranges listed herein include upper and lower limits. "Above" and "below" include endpoint values and all integers and fractions within the range, not limited to the specific values listed when the range is defined. The term "about" as used herein means that recipes, parameters, and other quantities and characteristics are not, and need not be, exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors, and measurement errors, etc. The term "and / or" as used herein is inclusive; for example, "A; and / or B" means only A, or only B, or both A and B.
[0107] In some embodiments of the present invention, the spinel phase in the glass-ceramic material having a spinel phase or in a glass-ceramic article having a spinel phase is preferably zinc aluminum spinel (ZnAl2O4). In some embodiments, the spinel phase has a higher weight percentage than other phases in the glass-ceramic material or the glass-ceramic article. In some embodiments, the spinel phase accounts for 20-60% of the weight of the glass-ceramic material or the glass-ceramic article, preferably 25-50%, more preferably 25-45%, and even more preferably 30-45%. In some embodiments, the spinel phase constitutes 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, or 60% of the weight of the glass-ceramic or glass-ceramic article.
[0108] In some embodiments of the present invention, the microcrystalline glass having a spinel phase or the microcrystalline glass article having a spinel phase contains a quartz phase (including both quartz and quartz solid solution), preferably, the quartz phase includes β-quartz solid solution. In some embodiments, the quartz phase accounts for 20% or less of the weight percentage of the microcrystalline glass or the microcrystalline glass article, preferably 10% or less, more preferably 5% or less, and even more preferably, the microcrystalline glass or the microcrystalline glass article does not contain a quartz phase. In some embodiments, the quartz phase constitutes 0%, greater than 0%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, and 20% of the glass-ceramic or glass-ceramic article by weight.
[0109] SiO2 is the network form of the glass-ceramic and glass-ceramic products of this invention. SiO2 can form a network structure using silicon-oxygen tetrahedral structural components, forming the basic structure of silicates. In some embodiments, SiO2 is also a necessary component for forming the quartz crystal phase. If the SiO2 content is too low, the chemical stability of the glass-ceramic and glass-ceramic products deteriorates; if the SiO2 content is too high, it will greatly increase the viscosity of the glass, raise the melting temperature, cause difficulties in material preparation, and increase the difficulty of forming the matrix glass. Therefore, the SiO2 content in this invention is 40-55%, preferably 45-53%, and more preferably 48-52%. In some embodiments, it may contain about 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, or 55% SiO2.
[0110] Al₂O₃ is beneficial for improving the mechanical properties and chemical stability of the microcrystalline glass and microcrystalline glass products of this invention, and is also a necessary component for the formation of the spinel crystal phase in this invention. Al₂O₃ can form [AlO₄] tetrahedra, replacing some [SiO₄] tetrahedra to form a network structure. The molecular volume of [AlO₄] tetrahedra is 41 cm⁻¹. 3 / mol, the molecular volume of [SiO4] tetrahedron is 27.2 cm³. 3 With [AlO4] tetrahedra replacing some [SiO4] tetrahedra per mol, the molecular volume increases and the structural network space expands, which is beneficial for the diffusion of alkali metal ions during chemical fortification and also facilitates the acceptance of a large amount of Na. + Al2O3 content promotes ion exchange. Too low an Al2O3 content hinders the strengthening effect and crystal precipitation, resulting in poor mechanical properties and chemical stability of the glass. Too high an Al2O3 content makes glass melting difficult, requires high melting temperatures, and easily leads to the precipitation of stones on the surface during forming. Therefore, the Al2O3 content is 15–30%, preferably 18–25%, and more preferably 20–23%. In some embodiments, it may contain about 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, or 30% Al2O3.
[0111] In some embodiments, controlling the SiO2 / Al2O3 ratio (SiO2 / Al2O3) within the range of 1.5 to 3.2 is beneficial for improving the drop ball test height and four-point bending strength of glass-ceramics and glass-ceramic products, as well as increasing the ion exchange layer depth and surface stress of glass-ceramic products. Therefore, a SiO2 / Al2O3 ratio of 1.5 to 3.2 is preferred, a SiO2 / Al2O3 ratio of 1.7 to 3.0 is more preferred, a SiO2 / Al2O3 ratio of 1.8 to 2.8 is even more preferred, and a SiO2 / Al2O3 ratio of 2.0 to 2.5 is even more preferred. In some implementations, the SiO2 / Al2O3 values are 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, 3.0, 3.05, 3.1, 3.15, and 3.2.
[0112] Li₂O can lower the melting point of glass and is also an essential component for chemical strengthening and improving the mechanical properties of glass-ceramic products. On the other hand, Li₂O can provide free oxygen, reducing TiO₂ coloration. Excessive Li₂O content leads to crystal growth in glass-ceramics and glass-ceramic products, and the crystal growth is unstable, affecting the transmittance of glass-ceramics and glass-ceramic products and deteriorating chemical stability. Therefore, the Li₂O content is 0.1%–6%, preferably 1%–5%, and more preferably 2%–4%. In some embodiments, it may contain about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, and 6% Li₂O.
[0113] ZnO is an essential component for the formation of the spinel crystalline phase in this invention. The spinel crystalline phase content can be controlled by adjusting the ZnO and Al2O3 content, thus ensuring both mechanical strength and transmittance. If the ZnO content is low, the crystalline phase content in the glass-ceramic and glass-ceramic products will be low, resulting in poor mechanical properties such as Vickers hardness and Young's modulus. If the ZnO content is too high, residual Zn in the glass phase will... 2+ The presence of ZnO hinders ion exchange during the chemical strengthening process, which is detrimental to obtaining high-performance glass-ceramic products. Therefore, the ZnO content is 9-20%, preferably 11-18%, and more preferably 12-16%. In some embodiments, it may contain about 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, or 20% ZnO.
[0114] In some embodiments, controlling the total content of Al2O3 and ZnO (Al2O3+ZnO) within the range of 26-45% is beneficial for obtaining the desired spinel crystal phase content in glass-ceramics and glass-ceramic products. This improves the drop resistance and drop ball test height of glass-ceramics and glass-ceramic products while preventing the deterioration of surface stress in the glass-ceramic products. Therefore, it is preferable that the Al2O3+ZnO content is 26-45%, more preferably 30-42%, further preferably 32-42%, and even more preferably 35-40%. In some embodiments, Al2O3+ZnO is 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, or 45%.
[0115] In some embodiments, controlling the ratio of Al2O3 content to ZnO content (Al2O3 / ZnO) within the range of 1.0 to 3.0 is beneficial for improving the hardness of glass-ceramics and glass-ceramic products, optimizing Young's modulus, and preventing a decrease in transmittance and a deterioration in haze. Therefore, an Al2O3 / ZnO ratio of 1.0 to 3.0 is preferred, more preferably 1.2 to 2.8, further preferably 1.25 to 2.5, and even more preferably 1.5 to 2.3. In some implementations, the Al2O3 / ZnO ratio is 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8, 2.85, 2.9, 2.95, or 3.0.
[0116] TiO2 is the nucleating agent for the glass-ceramic and glass-ceramic products of this invention. If the TiO2 content is too high, it will cause severe coloration (brownish-yellow) in the glass-ceramic and glass-ceramic products, reducing the transmittance in the visible light region and increasing haze and |B| value. Furthermore, excessive TiO2 content can easily cause the glass to emulsify during molding and crystallization, making the glass opaque. Therefore, the TiO2 content in this invention is 0.5-7%, preferably 1-6%, and more preferably 2-5%. In some embodiments, it may contain about 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, or 7% TiO2.
[0117] In some embodiments, controlling the ratio of Li₂O content to TiO₂ content (Li₂O / TiO₂) within the range of 0.2 to 4.5 can effectively reduce the Ti content in glass-ceramics and glass-ceramic products. 3+ The coloring by ions improves the transmittance of glass-ceramics and glass-ceramic products, and optimizes the haze and |B| value of glass-ceramics and glass-ceramic products. Therefore, the preferred Li2O / TiO2 ratio is 0.2 to 4.5, more preferably 0.5 to 3.5, even more preferably 0.7 to 2.5, and still more preferably 0.75 to 1.5. In some embodiments, the Li₂O / TiO₂ ratio is 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, or 1. 55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5.
[0118] In some embodiments, controlling the total content of TiO2 and ZnO, specifically the ratio of TiO2+ZnO to Al2O3 (TiO2+ZnO) / Al2O3, within the range of 0.4 to 1.5, can optimize the chemical strengthening properties of glass-ceramics, increase the ion exchange layer depth of glass-ceramic products, and improve fracture toughness, four-point bending strength, and drop ball test height. Therefore, it is preferable that (TiO2+ZnO) / Al2O3 is 0.4 to 1.5, more preferably 0.5 to 1.2, further preferably 0.6 to 1.0, and even more preferably 0.6 to 0.9. In some implementations, (TiO2+ZnO) / Al2O3 is 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, or 1.5.
[0119] ZrO2 can be used as a nucleating agent for glass-ceramics and glass-ceramic products. When used in conjunction with TiO2, it can maximize the number of crystal nuclei in the glass-ceramic. A higher number of nuclei is beneficial for stable crystal growth and uniform grain size. However, if the ZrO2 content is too high, the melting of the glass becomes more difficult. Therefore, the ZrO2 content is 0-5%, preferably 0.5-4%, and more preferably 1-3%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, etc. 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, and 5% ZrO2.
[0120] ZrO2 has low solubility in the glass system of this invention. In some embodiments, the solubility of ZrO2 in the glass can be improved by including a certain amount of P2O5; however, if too much P2O5 is present, the glass forming process is prone to phase separation, leading to a decrease in the chemical stability of the glass-ceramic and glass-ceramic products. Therefore, the content of P2O5 in this invention is 0-5%, preferably 0.5-4%, and more preferably 1-3%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, etc. 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, and 5% of P2O5.
[0121] In some embodiments, controlling the ratio of the total content of Al2O3 and Li2O (Al2O3+Li2O) to the content of P2O5 (Al2O3+Li2O) / P2O5 within the range of 5.0 to 45.0 is beneficial for improving the four-point bending strength and impact resistance of glass-ceramic and glass-ceramic products, and for increasing the surface stress of glass-ceramic products. Therefore, it is preferable that (Al2O3+Li2O) / P2O5 is 5.0 to 45.0, more preferably (Al2O3+Li2O) / P2O5 is 7.0 to 35.0, further preferably (Al2O3+Li2O) / P2O5 is 8.0 to 30.0, and even more preferably (Al2O3+Li2O) / P2O5 is 10.0 to 25.0. In some implementations, the ratio of (Al₂O₃+Li₂O) / P₂O₅ is 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, or 19.0. 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0.
[0122] In some embodiments, controlling the total content of P2O5 and ZrO2 (P2O5+ZrO2) within the range of 0-8% is beneficial for obtaining uniform grains and smaller grain sizes in glass-ceramics and glass-ceramic products, thereby optimizing the transmittance of the glass-ceramics and glass-ceramic products. Therefore, it is preferable that the content of P2O5+ZrO2 is 0-8%, more preferably 0.1-7%, and even more preferably 0.5-5%. In some embodiments, P2O5+ZrO2 is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%. %, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%.
[0123] In some embodiments, controlling the ratio of P2O5 content to ZrO2 content, P2O5 / ZrO2, within the range of 0.1 to 5.0, is beneficial for improving the hardness and fracture toughness of glass-ceramic and glass-ceramic products, and preventing a decrease in impact resistance and Young's modulus. Therefore, a P2O5 / ZrO2 ratio of 0.1 to 5.0 is preferred, a P2O5 / ZrO2 ratio of 0.2 to 3.0 is more preferred, a P2O5 / ZrO2 ratio of 0.5 to 2.0 is even more preferred, and a P2O5 / ZrO2 ratio of 0.6 to 1.5 is even more preferred. In some implementations, the P2O5 / ZrO2 ratio is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, or 5.0.
[0124] MgO helps reduce the viscosity of glass, inhibits glass crystallization during forming, refines grains during crystallization, and improves low-temperature melting properties. In some embodiments, MgO promotes the formation of quartz solid solution phases. If the MgO content is too high, quartz solid solution phases are easily formed during glass crystallization. The large grain size of quartz solid solution phases reduces the transmittance of glass-ceramics and glass-ceramic products. Therefore, the MgO content is 0.1–6%, preferably 1–5%, and more preferably 2–4%. In some embodiments, it may contain approximately 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, and 2.9%. % , 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6% MgO.
[0125] In some embodiments, controlling the total content of Li2O and MgO, and the ratio between the content of Li2O+MgO and TiO2 (Li2O+MgO) / TiO2, within the range of 0.3 to 8.0, can refine the grains, improve the transmittance and impact resistance of glass-ceramics and glass-ceramic products, and optimize the haze and |B| value of glass-ceramics and glass-ceramic products. Therefore, it is preferable that (Li2O+MgO) / TiO2 is 0.3 to 8.0, more preferably (Li2O+MgO) / TiO2 is 0.5 to 5.0, further preferably (Li2O+MgO) / TiO2 is 1.0 to 3.0, and even more preferably (Li2O+MgO) / TiO2 is 1.2 to 2.5. In some embodiments, the ratio of (Li₂O+MgO) / TiO₂ is 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, or 3.8. 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0.
[0126] In some embodiments, controlling the ratio of Al2O3 content to the total content of MgO and TiO2 (MgO+TiO2), Al2O3 / (MgO+TiO2), within the range of 1.3 to 10.0 is beneficial for improving the hardness and drop ball test height of glass-ceramics and glass-ceramic products, and optimizing the surface stress and haze of glass-ceramic products. Therefore, it is preferable that Al2O3 / (MgO+TiO2) is 1.3 to 10.0, more preferably 1.5 to 8.0, further preferably 2.5 to 6.5, and even more preferably 3.0 to 5.5. In some embodiments, the Al2O3 / (MgO+TiO2) ratio is 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3. 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.
[0127] B₂O₃ facilitates glass melting and improves the melting effect. However, if the B₂O₃ content is too high, the chemical stability of the glass deteriorates, and boron anomalies are more likely to occur, with the boron-oxygen tetrahedron structure transforming into a boron-oxygen trigonal structure, resulting in a decrease in glass viscosity. Furthermore, boron volatilization easily forms streaks, causing uneven glass. Therefore, the B₂O₃ content is 0–4%, preferably 0–2%, and more preferably 0–1%. In some embodiments, the composition may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, and 4% B2O3.
[0128] Na₂O can promote glass melting and improve the chemical strengthening properties of glass-ceramics. However, in this invention, excessive Na₂O content can lead to more broken bonds in the glass, reducing the strength of the matrix glass and consequently affecting the strength of the glass-ceramics and glass-ceramic products. Therefore, the upper limit of Na₂O content in this invention is 6%, preferably 4%, and more preferably 2%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, and 2.7%. 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, and 6% Na2O.
[0129] In some embodiments, controlling the ratio of the total SiO2 and Na2O content (SiO2+Na2O) to the ZnO content (SiO2+Na2O) / ZnO within the range of 2.2 to 6.2 can optimize the |B| value while improving the fracture toughness and compressive strength of glass-ceramics and glass-ceramic products. Therefore, it is preferable that (SiO2+Na2O) / ZnO is 2.2 to 6.2, more preferably (SiO2+Na2O) / ZnO is 2.5 to 6.0, further preferably (SiO2+Na2O) / ZnO is 2.8 to 5.5, and even more preferably (SiO2+Na2O) / ZnO is 3.0 to 5.0. In some implementations, (SiO2+Na2O) / ZnO is 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2.
[0130] K2O helps lower the glass melting temperature, which is beneficial for chemical strengthening and can increase the ion exchange layer depth of glass-ceramic products; however, if the K2O content is too high, it can easily lead to a decrease in the chemical stability and hardness of the glass. Therefore, the K2O content is 3% or less, preferably 2% or less, and more preferably 1% or less. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3% K2O.
[0131] In some embodiments, controlling the ratio of the total Na2O and K2O content (Na2O+K2O) to the ZnO content (Na2O+K2O) / ZnO to below 0.8 can refine the grains, reduce the grain size of the glass-ceramic and glass-ceramic products, improve the transmittance and compressive strength of the glass-ceramic and glass-ceramic products, and optimize the haze of the glass-ceramic and glass-ceramic products. Therefore, it is preferable that (Na2O+K2O) / ZnO is below 0.8, more preferably (Na2O+K2O) / ZnO is below 0.6, further preferably (Na2O+K2O) / ZnO is below 0.4, and even more preferably (Na2O+K2O) / ZnO is below 0.2. In some implementations, (Na2O+K2O) / ZnO is 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, or 0.8.
[0132] CaO, BaO, and SrO, acting as fluxes, do not participate in crystal phase formation and remain in the residual glass phase of the glass-ceramic. This is beneficial for lowering the melting and processing temperatures. However, excessively high content can impair nucleation and crystallization during the transformation of the matrix glass into glass-ceramics, adversely affecting the chemical stability of the glass-ceramic. Therefore, the total content of CaO, BaO, and SrO (CaO+BaO+SrO) is 0-5%, preferably 0-4%, and more preferably 0-2%. In some embodiments, the content of CaO+BaO+SrO is 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, and 2.1%. %, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%.
[0133] Y₂O₃ can promote the melting of ZrO₂ and reduce the difficulty of glass melting. However, excessive Y₂O₃ content can lead to difficulties in crystal formation during glass crystallization, resulting in a decrease in the drop ball test height of glass-ceramics and glass-ceramic products. Therefore, the upper limit of Y₂O₃ content is 6%, preferably 4%, and more preferably 2%. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, and 2.7%. 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, and 6% of Y2O3.
[0134] In some embodiments, the glass, glass-ceramic, or glass-ceramic articles may also contain 0-2% clarifying agent to improve the defoaming ability of the glass, glass-ceramic, or glass-ceramic articles. Such clarifying agents include, but are not limited to, one or more of Sb₂O₃, SnO₂, SnO, CeO₂, F (fluorine) compounds, Cl (chlorine) compounds, and Br (bromine) compounds, with Sb₂O₃ being preferred. When the above-mentioned clarifying agents are present alone or in combination, the upper limit of their content is preferably 2%, more preferably 1%, and even more preferably 0.5%. In some embodiments, the content of one or more clarifying agents is about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%.
[0135] Without affecting the performance of the glass, glass-ceramic, or glass-ceramic product of the present invention, other components not mentioned above, such as La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, and TeO2, may be appropriately added. However, to maintain the excellent performance of the glass, glass-ceramic, or glass-ceramic product of the present invention, the content of each of La2O3, Gd2O3, Yb2O3, Nb2O5, WO3, Bi2O3, Ta2O5, and TeO2, or their combined content, is preferably 5% or less, more preferably 2% or less, further preferably 1% or less, and even more preferably not contained in any of them.
[0136] PbO and As2O3 are toxic substances, and even small amounts do not meet environmental protection requirements. Therefore, in some embodiments of the present invention, it is preferable that PbO and / or As2O3 are not present.
[0137] In some embodiments of the present invention, colored matrix glass, glass-ceramics, or glass-ceramic products can be prepared by including colorants, allowing the matrix glass, glass-ceramics, or glass-ceramic products to exhibit different colors. The colorants contain: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O5: 0-8%; and / or CeO2: 0-4%. The weight percentage content of the colorants and their functions are detailed below:
[0138] The brown or green matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use NiO, Ni2O3, or Pr2O5 as colorants. NiO and Ni2O3 are used as colorants in the preparation of brown or green matrix glass, microcrystalline glass, or microcrystalline glass products. The two components can be used alone or in combination, and their respective contents are generally below 4%, preferably below 3%. If the content exceeds 4%, the colorant cannot dissolve well in the matrix glass, microcrystalline glass, or microcrystalline glass products. The lower limit of their respective contents is above 0.1%. If it is below 0.1%, the color of the matrix glass, microcrystalline glass, or microcrystalline glass products is not obvious. In some embodiments, the mixture may contain approximately 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4.0% NiO or Ni2O3. When used in combination, the total amount of NiO and Ni2O3 is generally below 4%, with a lower limit of above 0.1%. In some embodiments, the composition may include approximately 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, and 4.0% of NiO and Ni2O3. When Pr2O5 is used as a colorant for green matrix glass, glass-ceramic, or glass-ceramic products, it is used alone, and its content is generally below 8%, preferably below 6%, with a lower limit of 0.4%. If the content is below 0.4%, the color of the matrix glass, glass-ceramic, or glass-ceramic products will not be obvious.In some embodiments, it may contain about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, and 8.0% Pr2O5.
[0139] The blue matrix glass, glass-ceramic, or glass-ceramic products prepared by this invention use CoO or Co2O3 as colorants. The two colorant components can be used alone or in combination, and their respective contents are generally below 2%, preferably below 1.8%. If the content exceeds 2%, the colorant cannot dissolve well in the matrix glass, glass-ceramic, or glass-ceramic products. The lower limit of their respective contents is above 0.05%. If it is below 0.05%, the color of the matrix glass, glass-ceramic, or glass-ceramic products is not obvious. In some embodiments, it may contain about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2.0% CoO or Co2O3. When used in combination, the total amount of CoO and Co2O3 shall not exceed 2%, with a lower limit of 0.05%. In some embodiments, it may contain approximately 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2.0% of CoO and Co2O3.
[0140] The yellow matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use Cu2O or CeO2 as colorants. The two colorant components are used alone or in combination, and their respective contents are limited to 0.5% or more. If the content is less than 0.5%, the color of the matrix glass, microcrystalline glass, or microcrystalline glass products will not be obvious. When Cu2O is used alone, the content is less than 4%, preferably less than 3%. If the content exceeds 4%, it will easily cause the matrix glass to crystallize. In some embodiments, it may contain about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4.0% Cu2O. When used alone, the CeO2 content is generally below 4%, preferably below 3%. If the content exceeds 4%, the gloss of the matrix glass, glass-ceramic, or glass-ceramic products will be poor. In some embodiments, CeO2 may be included in the glass at concentrations of approximately 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, and 4.0%. Simultaneously, the addition of a small amount of CeO2 to the glass has a defoaming effect. CeO2 can also be used as a clarifying agent in the glass, with a content of 2% or less, preferably 1% or less, and more preferably 0.5% or less. When two colorants are used in combination, their combined amount is generally below 4%, with a lower limit of 0.5% or higher. In some embodiments, it may contain about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4.0% CeO2 and Cu2O.
[0141] The black or smoky gray matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use Fe2O3 as the colorant alone; or a mixture of Fe2O3 and CoO as the colorant; or a mixture of Fe2O3 and Co2O3 as the colorant; or a mixture of Fe2O3, CoO, and NiO as the colorant; or a mixture of Fe2O3, Co2O3, and NiO as the colorant. The colorant used in preparing the black and smoky gray matrix glass, microcrystalline glass, or microcrystalline glass products mainly uses Fe2O3, with a content of less than 7%, preferably less than 5%, and a lower limit of more than 0.2%. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, or 1.6%. The concentrations of Fe2O3 are 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, and 7.0%. CoO and Co2O3 absorb visible light and can deepen the color of the matrix glass, glass-ceramic, or glass-ceramic products. Generally, when used in combination with Fe2O3, their individual contents are below 0.6%, with a lower limit above 0.2%. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, or 0.6% CoO and / or Co2O3. NiO absorbs visible light and can deepen the color of the matrix glass, glass-ceramic, or glass-ceramic articles. When used in combination, its content is generally less than 1%, with a lower limit of total content above 0.2%. In some embodiments, it may contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0% NiO.
[0142] The purple matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use MnO2 as a colorant, and the content is generally below 4%, preferably below 3%, with a lower limit of 0.1% or more. If it is below 0.1%, the color of the matrix glass, microcrystalline glass, or microcrystalline glass products will not be obvious. In some embodiments, it may contain about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, or 4.0% MnO2.
[0143] The pink matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use Er₂O₃ as a colorant, with a content generally below 8%, preferably below 6%. Because the rare earth element Er₂O₃ has low coloring efficiency, even when the content exceeds 8%, it cannot further deepen the color of the matrix glass, microcrystalline glass, or microcrystalline glass products, but instead increases costs. Its lower limit is above 0.4%; if it is below 0.4%, the color of the matrix glass, microcrystalline glass, or microcrystalline glass products is not obvious. In some embodiments, it may contain about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, and 8.0% Er2O3.
[0144] The purplish-red matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use Nd₂O₃ as a colorant, with a content generally below 8%, preferably below 6%. Because the coloring efficiency of rare earth element Nd₂O₃ is low, even a content exceeding 8% will not further deepen the color of the matrix glass, microcrystalline glass, or microcrystalline glass products, but will instead increase costs. Therefore, its content is limited to above 0.4%; if it is below 0.4%, the color of the matrix glass, microcrystalline glass, or microcrystalline glass products will be indistinct. In some embodiments, it may contain about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, and 8.0% Nd2O3.
[0145] The red matrix glass, microcrystalline glass, or microcrystalline glass products prepared by this invention use a mixed colorant of Er2O3, Nd2O3, and MnO2. Er ions in the glass have absorption at 400-500 nm, Mn ions mainly have absorption at 500 nm, and Nd ions mainly have strong absorption at 580 nm. The mixture of these three substances can prepare red matrix glass, microcrystalline glass, or microcrystalline glass products. Since Er2O3 and Nd2O3 are rare earth colorants, their coloring ability is relatively weak. The amount of Er2O3 used is less than 6%, the amount of Nd2O3 used is less than 4%, and MnO2 has strong coloring ability. Its amount used is within 2%. The lower limit of the total amount of the mixed colorant used is above 0.9%.
[0146] The terms "not containing" and "0%" as used herein mean that the compound, molecule, or element was not intentionally added as a raw material to the matrix glass, glass-ceramic, or glass-ceramic product of this invention. However, as raw materials and / or equipment used in the production of matrix glass, glass-ceramic, or glass-ceramic products, there may be certain impurities or components that are not intentionally added, which may be present in small or trace amounts in the final matrix glass, glass-ceramic, or glass-ceramic product. Such cases are also within the scope of protection of this patent.
[0147] The grain size and crystal phase type of the microcrystalline glass or microcrystalline glass product of the present invention affect the haze and light transmittance of the microcrystalline glass or microcrystalline glass product; the smaller the grain size, the higher the light transmittance; the lower the haze, the higher the light transmittance. In some embodiments, the haze of the microcrystalline glass product or microcrystalline glass with a thickness of less than 1 mm is less than 0.3%, preferably less than 0.25%, and more preferably 0.05-0.2%. In some embodiments, the grain size of the microcrystalline glass product or microcrystalline glass is less than 60 nm, preferably less than 45 nm, and more preferably 10-30 nm.
[0148] In some embodiments, the crystalline phase content and refractive index of the microcrystalline glass or microcrystalline glass product of the present invention affect the |B| value of the microcrystalline glass or microcrystalline glass product. When observed in the visible light range, the microcrystalline glass or microcrystalline glass product appears bluish or yellowish, affecting the optical performance of the product. This is indicated by the |B| value in LAB (Colorimetric Alternate B) standards. The microcrystalline glass or microcrystalline glass product of the present invention exhibits a low |B| value in the visible light range. In some embodiments, the average optical |B| value at 400–800 nm for microcrystalline glass products or microcrystalline glass with a thickness of less than 1 mm is 1.0 or less, preferably 0.8 or less, and more preferably 0.3–0.6.
[0149] In some embodiments, the microcrystalline glass or microcrystalline glass article of the present invention exhibits high transparency in the visible light range (i.e., the microcrystalline glass or microcrystalline glass article is transparent). The microcrystalline glass or microcrystalline glass article exhibits high transmittance in the visible light range. In some embodiments, the average light transmittance of the microcrystalline glass article or microcrystalline glass with a thickness of 1 mm or less at 400–800 nm is preferably 87.0% or more, more preferably 88.5% or more, and even more preferably 89.5% or more. In some preferred embodiments, the light transmittance of the microcrystalline glass article or microcrystalline glass with a thickness of 1 mm or less at 550 nm is preferably 87.0% or more, more preferably 88.0% or more, and even more preferably 89.0% or more.
[0150] In some embodiments, antimicrobial components may be added to the substrate glass, glass-ceramic, or glass-ceramic articles. The glass-ceramic or glass-ceramic articles described herein can be used in applications such as kitchen or dining countertops, where exposure to harmful bacteria is likely. The antimicrobial components contained in the substrate glass, glass-ceramic, or glass-ceramic articles include, but are not limited to, Ag, AgO, Cu, CuO, Cu2O, etc. In some embodiments, the content of the above-mentioned antimicrobial components, individually or in combination, is 2% or less, preferably 1% or less.
[0151] The matrix glass, the microcrystalline glass having a spinel crystal phase, and the microcrystalline glass article having a spinel crystal phase of the present invention can be produced and manufactured by the following method:
[0152] Forming the matrix glass: The raw materials (oxides, hydroxides, complex salts, etc.) are mixed evenly according to the component ratio, and then placed in a crucible (e.g., a platinum or quartz crucible). Depending on the melting difficulty of the glass composition, melting is carried out in an electric or gas furnace at a temperature range of 1350–1550°C for 5–24 hours, preferably at a melting temperature of 1450–1550°C. The matrix glass is then obtained after clarification, homogenization, shaping, and annealing. The clarification temperature is preferably greater than 1550°C but less than or equal to 1650°C, and the annealing temperature is preferably 450–600°C.
[0153] The matrix glass of the present invention can be formed by well-known methods.
[0154] The matrix glass of this invention undergoes a crystallization process after molding or processing, resulting in uniform crystal precipitation within the glass to form a microcrystalline glass. This crystallization process can be performed in one stage or two stages, preferably in two stages. The two-stage crystallization process involves a nucleation process at a first temperature followed by a crystal growth process at a second temperature. The crystallization process performed at the first temperature is referred to as the first crystallization process, and the crystallization process performed at the second temperature is referred to as the second crystallization process.
[0155] To achieve the desired physicochemical properties in glass-ceramics, the preferred crystallization process is as follows:
[0156] The crystallization process described above, performed in a single stage, allows for continuous nucleation and crystal growth. Specifically, the temperature is raised to a predetermined crystallization temperature, maintained for a certain period, and then cooled. The preferred crystallization temperature is 600–800°C, but more preferably 650–750°C to precipitate the desired crystalline phase. The holding time at the crystallization temperature is preferably 1–10 hours, more preferably 3–6 hours.
[0157] When the crystallization process is carried out in two stages, the first temperature is preferably 600-700°C, the second temperature is preferably greater than 700°C but less than or equal to 800°C, the holding time at the first temperature is preferably 1-6 hours, and the holding time at the second temperature is preferably 2-5 hours.
[0158] In some embodiments, the matrix glass or glass-ceramic described herein can be manufactured into shaped bodies using various processes, including but not limited to sheets, and the processes include but not limited to slot drawing, float glass, roll forming, and other sheet forming processes known in the art. Alternatively, the matrix glass or glass-ceramic can be formed using float glass or roll forming methods known in the art. The shaped bodies described in this invention also include lenses, prisms, etc.
[0159] The matrix glass or microcrystalline glass of the present invention can be manufactured into sheet glass or microcrystalline glass by methods such as grinding or polishing, but the method of manufacturing the glass or microcrystalline glass is not limited to these methods.
[0160] The matrix glass or microcrystalline glass of the present invention can be prepared into various shapes of glass molded bodies or microcrystalline glass molded bodies by means of hot bending process or molding process at a certain temperature, but is not limited to these methods.
[0161] In some embodiments, a hot bending process can be used to produce glass molded bodies or microcrystalline glass molded bodies. The hot bending process involves placing 2D or 2.5D glass or microcrystalline glass in a mold and sequentially performing steps such as heating and preheating, pressing and forming, and holding and cooling in a hot bending machine to obtain a 3D curved glass molded body or microcrystalline glass molded body.
[0162] In some embodiments, the glass-ceramic molded body has a 2.5D or 3D structure, i.e., the glass-ceramic molded body has a non-planar structure. As used herein, "non-planar structure" means that in a 2.5D or 3D shape, at least a portion of the glass-ceramic molded body extends outward or along an angle with a plane defined by the original, layout configuration of the 2D matrix glass. The 2.5D or 3D glass-ceramic molded body formed from the matrix glass may have one or more protrusions or curved portions.
[0163] The matrix glass, microcrystalline glass having a spinel phase, and microcrystalline glass articles having a spinel phase described in this invention can have any reasonably useful thickness.
[0164] In addition to improving mechanical properties through precipitation crystallization, the microcrystalline glass with spinel phase of the present invention can also obtain superior mechanical properties by forming a compressive stress layer, thereby producing microcrystalline glass products with spinel phase.
[0165] In some embodiments, the substrate glass or microcrystalline glass can be processed into sheets and / or shaped (such as drilling, hot bending, etc.), polished and / or swept after shaping, and then chemically strengthened through a chemical strengthening process.
[0166] The chemical strengthening method described in this invention is ion exchange. During ion exchange, smaller metal ions in the matrix glass or glass-ceramic are replaced or "exchanged" by larger metal ions with the same valence state located near the matrix glass or glass-ceramic. Replacing smaller ions with larger ions creates compressive stress in the matrix glass or glass-ceramic, forming a compressive stress layer.
[0167] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na+). + K+ 、Rb + Cs + Ion exchange is carried out by immersing a matrix glass or glass-ceramic in a salt bath containing at least one molten salt containing larger metal ions, which replace smaller metal ions in the matrix glass. Alternatively, other monovalent metal ions such as Ag can be used. + 、Tl + Cu + Ion exchange processes can also be used to exchange monovalent ions. One or more ion exchange processes used to chemically strengthen matrix glass or glass-ceramics may include, but are not limited to, immersion in a single salt bath, or immersion in multiple salt baths having the same or different compositions, with washing and / or annealing steps between immersions.
[0168] In some embodiments, the matrix glass or glass-ceramic can be ion-exchanged by immersion in a salt bath of molten Na salt (such as NaNO3) at a temperature of about 350–470°C for about 1–36 hours, preferably at a temperature range of 400–460°C, and preferably for a time range of 2–15 hours. In this embodiment, Na ions replace some of the Li ions in the matrix glass or glass-ceramic, thereby forming a surface compression layer and exhibiting high mechanical properties. In some embodiments, the matrix glass or glass-ceramic can be ion-exchanged by immersion in a mixed salt bath of molten K salt and Na salt at a temperature of about 360–450°C for 1–36 hours, preferably for a time range of 2–24 hours.
[0169] The microcrystalline glass with a spinel crystal phase involved in this invention exhibits highly efficient low-temperature ion exchange performance. In some embodiments, at relatively low ion exchange temperatures and short exchange times, the exchange layer depth of Na ions can reach over 75 μm. After ion exchange, the hardness of the microcrystalline glass with a spinel crystal phase is significantly improved. This is mainly because ion exchange, through a "squeezing effect," creates high compressive stress on the surface of the microcrystalline glass with a spinel crystal phase, thereby increasing the deformation resistance and hardness of the microcrystalline glass with a spinel crystal phase. In some embodiments, after chemical strengthening, the microcrystalline glass with a spinel crystal phase of this invention can achieve a Vickers hardness of up to 650 kgf / mm². 2 above.
[0170] The performance indicators of the microcrystalline glass with spinel crystal phase and / or microcrystalline glass products with spinel crystal phase of the present invention are tested using the following methods:
[0171] [Haze]
[0172] The Minolta CM3600A haze meter was used to prepare samples with a thickness of less than 1 mm, and the test was conducted according to GB2410-80 standard.
[0173] [Grain Size]
[0174] The size of the crystallites was determined by scanning electron microscopy (SEM) after surface treatment with HF acid followed by gold sputtering.
[0175] [Light transmittance]
[0176] The light transmittance mentioned in this article refers to external transmittance, sometimes simply referred to as transmittance.
[0177] The sample was processed to a size of less than 1 mm and its opposite surfaces were polished in parallel. The average light transmittance of 400–800 nm was measured using a Hitachi U-41000 spectrophotometer.
[0178] The sample was processed to a size of less than 1 mm and its surfaces were polished in parallel. The light transmittance at 550 nm was measured using a Hitachi U-41000 spectrophotometer.
[0179] [Ion exchange layer depth]
[0180] The depth of the ion exchange layer was determined using a glass surface stress meter SLP-2000.
[0181] The measurement conditions were calculated with the sample's refractive index being 1.56 and its optical elastic constant being 29 [(nm / cm) / MPa].
[0182] [Surface Stress]
[0183] Surface stress was measured using a glass surface stress meter SLP-2000.
[0184] The measurement conditions were calculated with the sample's refractive index being 1.56 and its optical elastic constant being 29 [(nm / cm) / MPa].
[0185] [Drop resistance]
[0186] Drop resistance testing was conducted using a WH-2101 drop tester. Two identical glass products (each weighing 20g, load) were loaded onto a 2D microcrystalline glass product. 60-80 grit sandpaper was placed on a base, and the product was dropped freely from a specified height, directly impacting the sandpaper. The drop resistance was measured from the height from which the product could withstand the impact without breaking. Specifically, the test started at a height of 600mm, and then increased to 700mm, 800mm, 900mm, 1000mm, and higher without breakage. For examples demonstrating "drop resistance," microcrystalline glass products were used as the test subject. In this example, test data recorded at 1000mm indicates that the microcrystalline glass product withstood the impact without breaking even when loaded from a height of 1000mm. The maximum test height for the WH-2101 drop tester was 2000mm.
[0187] [Drop test height]
[0188] A 145mm × 67mm × 0.7mm microcrystalline glass sample is placed on a glass bearing fixture, and a 132g steel ball is dropped from a specified height, with the impact point being the center of the sample. The maximum drop ball test height from which the sample can withstand the impact without breaking is determined. Specifically, the drop ball test begins at a height of 400mm, with each drop occurring once at each height. If the sample does not break, the height is increased by 100mm each time, continuing the test until the sample breaks. In the embodiment with a "drop ball test height," the microcrystalline glass product is used as the test object. In this embodiment, the test data is recorded as 1700mm, indicating that the microcrystalline glass product withstood the impact without breaking even when a steel ball is dropped from a height of 1700mm. In this invention, the drop ball test height is sometimes simply referred to as the drop ball height.
[0189] [Fracture toughness]
[0190] The method of directly measuring the indentation-propagated crack size was used. The sample size was 2mm×4mm×20mm. After chamfering, grinding and polishing, the sample was prepared. A force of 49N was applied to the sample with a Vickers hardness indenter and maintained for 30s to make an indentation. The fracture strength was determined by the three-point bending method.
[0191] [Four-point bending strength]
[0192] A CMT6502 microcomputer-controlled electronic universal testing machine was used, with sample thicknesses of less than 1 mm (preferably 0.7 mm), and testing was conducted according to ASTM C 158-2002. In this invention, the four-point bending strength is sometimes simply referred to as bending strength.
[0193] Vickers hardness
[0194] The load (N) when a diamond pyramidal indenter with a 136° angle between its two faces is pressed into a pyramid-shaped indentation on the test surface is divided by the surface area (mm) calculated from the length of the indentation. 2 The value is represented by ). The test is conducted with a load of 100 (N) and a holding time of 15 (seconds). In this invention, Vickers hardness is sometimes simply referred to as hardness.
[0195] [Compressive strength]
[0196] A CMT6502 microcomputer-controlled electronic universal testing machine was used. A 145mm × 67mm × 0.7mm microcrystalline glass sample was placed on a glass bearing fixture. The compression rod had a mushroom-head design with a diameter of ¢10mm, and the compression speed was 5mm / min until the sample broke. Calibration with a fixture was required before testing, and the test point was at the center. The test button was pressed until the microcrystalline glass sample was crushed, and the pressure (N) at the time of sample breakage was recorded. For the embodiment with "compression strength," the microcrystalline glass was used as the test object. In this embodiment, the test data recorded as 500N indicates that the maximum compressive force the microcrystalline glass could withstand before breakage was 500N.
[0197] [|B| value]
[0198] B-value testing was performed using a Minolta CM-700d. Samples were less than 1 mm thick. The instrument was calibrated at zero position and on a white board using the matching calibration long and short tubes, respectively. After calibration, an air test was performed using the long tube to determine the instrument's stability and calibration reliability (B≤0.05). After the instrument was calibrated successfully, the product was placed on the zero-position long tube for testing.
[0199] The |B| value is the absolute value of the B value.
[0200] Young's modulus
[0201] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.
[0202]
[0203] G = V S 2 ρ
[0204] In the formula: E is Young's modulus, Pa;
[0205] G is the shear modulus, Pa;
[0206] V T The transverse wave velocity is in m / s;
[0207] V S The longitudinal wave velocity is given in m / s.
[0208] ρ is the density of glass, in g / cm³ 3 .
[0209] The microcrystalline glass products of the present invention having a spinel crystal phase have the following properties:
[0210] 1) In some embodiments, the grain size of the microcrystalline glass article having spinel phase is 60 nm or less, preferably 45 nm or less, and more preferably 10 to 30 nm.
[0211] 2) In some embodiments, the ion exchange layer depth of the microcrystalline glass product having a spinel crystal phase is 75 μm or more, preferably 80 to 150 μm, and more preferably 100 to 125 μm.
[0212] 3) In some embodiments, the surface stress of the microcrystalline glass article having spinel phase is 200 MPa or more, preferably 250 to 400 MPa, and more preferably 300 to 400 MPa.
[0213] 4) In some embodiments, the drop ball test height of the microcrystalline glass article having spinel phase is 1000 mm or more, preferably 1200 mm or more, and more preferably 1500 mm or more.
[0214] 5) In some embodiments, the drop resistance of the microcrystalline glass article having spinel phase is 1200 mm or more, preferably 1300 mm or more, and more preferably 1400 mm or more.
[0215] 6) In some embodiments, the fracture toughness of the microcrystalline glass article having a spinel crystal phase is 1.0 MPa·m. 1 / 2 The above is preferably 1.2 MPa·m 1 / 2 The above, more preferably 1.2 to 1.6 MPa·m 1 / 2 .
[0216] 7) In some embodiments, the four-point bending strength of the microcrystalline glass article having spinel phase is 500 MPa or more, preferably 600 MPa or more, and more preferably 700 to 1000 MPa.
[0217] 8) In some embodiments, the microcrystalline glass article having spinel phase has a compressive strength of 400 N or more, preferably 400 to 550 N, and more preferably 450 to 550 N.
[0218] 9) In some embodiments, the Vickers hardness (H) of microcrystalline glass articles having a spinel crystal phase is... v ) is 650 kgf / mm 2 The preferred value is 660 kgf / mm². 2The above, more preferably 680–750 kgf / mm 2 .
[0219] 10) In some embodiments, the haze of the microcrystalline glass article with spinel phase and a thickness of less than 1 mm is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0220] 11) In some embodiments, the microcrystalline glass article having a spinel crystal phase and a thickness of less than 1 mm has an average light transmittance of 87.0% or more at a wavelength of 400-800 nm, preferably 88.5% or more, more preferably 89.5% or more. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0221] 12) In some embodiments, the microcrystalline glass article having a spinel crystal phase and a thickness of less than 1 mm has a light transmittance of 87.0% or more at a wavelength of 550 nm, preferably 88.0% or more, more preferably 89.0% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0222] 13) In some embodiments, the microcrystalline glass article having a spinel crystal phase and a thickness of less than 1 mm has an average optical |B| value of 1.0 or less at 400-800 nm, preferably less than 0.8, more preferably 0.3-0.6. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0223] The microcrystalline glass of this invention having a spinel crystal phase has the following properties:
[0224] 1) In some embodiments, the grain size of the microcrystalline glass having a spinel phase is 60 nm or less, preferably 45 nm or less, and more preferably 10 to 30 nm.
[0225] 2) In some embodiments, the haze of the microcrystalline glass with a spinel phase and a thickness of less than 1 mm is 0.3% or less, preferably 0.25% or less, more preferably 0.05 to 0.2%. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0226] 3) In some embodiments, the microcrystalline glass with a spinel crystal phase and a thickness of less than 1 mm has an average light transmittance of 87.0% or more at a wavelength of 400-800 nm, preferably 88.5% or more, more preferably 89.5% or more. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0227] 4) In some embodiments, the microcrystalline glass with a spinel crystal phase and a thickness of less than 1 mm has a light transmittance of 87.0% or more at a wavelength of 550 nm, preferably 88.0% or more, more preferably 89.0% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0228] 5) In some embodiments, the glass-ceramic material with a spinel crystal phase and a thickness of less than 1 mm has an average optical |B| value of 1.0 or less at 400–800 nm, preferably less than 0.8, more preferably 0.3–0.6. The thickness is preferably 0.2–1 mm, more preferably 0.3–0.9 mm, further preferably 0.5–0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.
[0229] 6) In some embodiments, the Young's modulus (E) of the microcrystalline glass having a spinel phase is 80 to 110 GPa, preferably 85 to 105 GPa, and more preferably 90 to 105 GPa.
[0230] 7) In some embodiments, the Vickers hardness (H) of the microcrystalline glass having a spinel phase is... v ) is 550 kgf / mm 2 The preferred value is 580 kgf / mm². 2 The above, more preferably 600-650 kgf / mm 2 .
[0231] Due to the aforementioned superior properties, the microcrystalline glass, microcrystalline glass products, matrix glass, glass molded body, and microcrystalline glass molded body of the present invention can be widely used to manufacture glass covers or glass components. Furthermore, the microcrystalline glass, microcrystalline glass products, matrix glass, glass molded body, and microcrystalline glass molded body of the present invention can be applied to electronic devices or display devices, such as mobile phones, watches, computers, and touch screens. They can be used to manufacture protective glass for mobile phones, smartphones, tablet computers, laptops, PDAs, televisions, personal computers, MTA machines, or industrial displays; or to manufacture touch screens, protective windows, car windows, train windows, aircraft mechanical windows, and touch screen protective glass; or to manufacture hard disk substrates or solar cell substrates; or to manufacture white goods, such as refrigerator components or kitchenware.
[0232] Example
[0233] To further clarify and illustrate the technical solution of the present invention, the following non-limiting embodiments are provided. While the embodiments of the present invention have made considerable efforts to ensure the accuracy of numerical values (e.g., quantities, temperatures, etc.), some errors and deviations must be taken into account. The composition itself is based on oxides and is given in weight percent, and has been normalized to 100%.
[0234] <Examples of microcrystalline glass with spinel phase>
[0235] In this embodiment, the microcrystalline glass with spinel phase and the composition shown in Tables 1 to 4 were obtained by using the above-described method for manufacturing microcrystalline glass with spinel phase. Furthermore, the characteristics of each microcrystalline glass were measured using the testing method described in this invention, and the measurement results are shown in Tables 1 to 4. In the following embodiments, the test sample thickness for haze, average light transmittance at wavelengths of 400–800 nm, light transmittance at wavelength of 550 nm, and average light |B| value at wavelengths of 400–800 nm was 0.7 mm.
[0236] Table 1.
[0237]
[0238] Table 2.
[0239]
[0240]
[0241] Table 3.
[0242]
[0243]
[0244] Table 4.
[0245]
[0246]
[0247] <Examples of microcrystalline glass products with spinel crystal phase>
[0248] In this embodiment, the microcrystalline glass articles with spinel crystal phases having the compositions shown in Tables 5 to 8 were obtained using the manufacturing method described above. Furthermore, the characteristics of each microcrystalline glass article with spinel crystal phase were measured using the testing method described in this invention, and the measurement results are shown in Tables 5 to 8. In the following examples, the test sample thickness for haze, average light transmittance at wavelengths of 400–800 nm, light transmittance at wavelength of 550 nm, and average light |B| value at wavelengths of 400–800 nm was 0.7 mm.
[0249] Table 5.
[0250]
[0251]
[0252] Table 6.
[0253]
[0254]
[0255] Table 7.
[0256]
[0257]
[0258] Table 8.
[0259]
[0260]
Claims
1. A microcrystalline glass product having a spinel crystal phase, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 41–55%; Al2O3+ZnO: 26–45%; Li2O: 0.1–6%; MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, of which Li2O / TiO2 is 0.4–4.5, Al2O3 / ZnO is 1.0–3.0, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass products with a thickness of less than 1 mm is below 0.3%, and the average optical |B| value of 400–800 nm is below 0.
8.
2. The microcrystalline glass product with spinel crystal phase according to claim 1, characterized in that, Its components, expressed as a percentage by weight, also include: P2O5+ZrO2: 0–8%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Y2O3: 0–6%; and / or clarifying agent: 0–2%.
3. A microcrystalline glass product having a spinel crystal phase, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 41–55%; Al2O3+ZnO: 26–45%; Li2O: 0.1–6%; MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, wherein Al2O3 / ZnO is 1.0–3.0, Li2O / TiO2 is 0.4–4.5, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass products with a thickness of less than 1 mm is below 0.3%, the average light |B| value of 400–800 nm is below 0.8, and the light transmittance of microcrystalline glass products with a thickness of less than 1 mm at a wavelength of 550 nm is above 87.0%.
4. A microcrystalline glass product having a spinel crystal phase, characterized in that, The microcrystalline glass product has a drop ball test height of 1000 mm or more, and its composition, expressed as a weight percentage, contains: SiO2: 41-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%. MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, wherein Al2O3 / ZnO is 1.0–3.0, Li2O / TiO2 is 0.4–4.5, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass products with a thickness of less than 1 mm is below 0.3%, and the average optical |B| value of 400–800 nm is below 0.
8.
5. The microcrystalline glass article having a spinel crystal phase according to claim 3 or 4, characterized in that, Its components, expressed as a percentage by weight, also include: P2O5+ZrO2: 0–8%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Y2O3: 0–6%; and / or clarifying agent: 0–2%.
6. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: Li2O / TiO2 is 0.5–3.5; and / or Al2O3 / ZnO is 1.2–2.8; and / or SiO2 / Al2O3 is 1.5–3.2; and / or (TiO2+ZnO) / Al2O3 is 0.4–1.5; and / or (Li2O+MgO) / TiO2 is 1.0–2.9; and / or (Al2O3+Li2O) / P2O5 is 5.0–45.0; and / or P2O5 / ZrO2 is 0.1–5.0; and / or (SiO2+Na2O) / ZnO is 2.2–6.2; and / or (Na2O+K2O) / ZnO is less than 0.
4.
7. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: Li2O / TiO2 is 0.7–2.5; and / or Al2O3 / ZnO is 1.5–2.5; and / or SiO2 / Al2O3 is 1.7–3.0; and / or (TiO2+ZnO) / Al2O3 is 0.5–1.2; and / or (Li2O+MgO) / TiO2 is 1.2–2.5; and / or Al2O3 / (MgO+TiO2) is 2.5–6.5; and / or (Al2O3+Li2O) / P2O5 is 7.0–35.0; and / or P2O5 / ZrO2 is 0.2–3.0; and / or (SiO2+Na2O) / ZnO is 2.5–6.0; and / or (Na2O+K2O) / ZnO is less than 0.
2.
8. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: Li2O / TiO2 is 0.75–1.5; and / or Al2O3 / ZnO is 1.5–2.3; and / or SiO2 / Al2O3 is 1.8–2.8; and / or (TiO2+ZnO) / Al2O3 is 0.6–1.0; and / or Al2O3 / (MgO+TiO2) is 3.0–5.5; and / or (Al2O3+Li2O) / P2O5 is 8.0–30.0; and / or P2O5 / ZrO2 is 0.5–2.0; and / or (SiO2+Na2O) / ZnO is 2.8–5.
5.
9. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Al2O3 is 2.0 to 2.5; and / or (TiO2+ZnO) / Al2O3 is 0.6 to 0.9; and / or (Al2O3+Li2O) / P2O5 is 10.0 to 25.0; and / or P2O5 / ZrO2 is 0.6 to 1.5; and / or (SiO2+Na2O) / ZnO is 3.0 to 5.
0.
10. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: SiO2: 45–53%; and / or Al2O3+ZnO: 30–42%; and / or Li2O: 1–5%; and / or MgO: 1–5%; and / or TiO2: 1–6%; and / or P2O5+ZrO2: 0.1–7%; and / or Na2O: 0–4%; and / or B2O3: 0–2%; and / or K2O: 0–2%; and / or CaO+BaO+SrO: 0–4%; and / or Y2O3: 0–4%; and / or clarifying agent: 0–1%.
11. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: SiO2: 48–52%; and / or Al2O3+ZnO: 32–42%; and / or Li2O: 2–4%; and / or MgO: 2–4%; and / or TiO2: 2–5%; and / or P2O5+ZrO2: 0.5–5%; and / or Na2O: 0–2%; and / or B2O3: 0–1%; and / or K2O: 0–1%; and / or CaO+BaO+SrO: 0–2%; and / or Y2O3: 0–2%; and / or clarifying agent: 0–0.5%.
12. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its composition, expressed as a percentage by weight, contains: Al2O3 + ZnO: 35-40%.
13. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 15-30%; and / or ZnO: 9-20%; and / or P2O5: 0-5%; and / or ZrO2: 0-5%.
14. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 18–25%; and / or ZnO: 11–18%; and / or P2O5: 0.5–4%; and / or ZrO2: 0.5–4%.
15. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 20–23%; and / or ZnO: 12–16%; and / or P2O5: 1–3%; and / or ZrO2: 1–3%.
16. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Spinel crystal phase accounts for 20-60% of the weight of glass-ceramic products.
17. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Spinel crystal phase accounts for 25-50% of the weight of glass-ceramic products.
18. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Spinel crystal phase accounts for 25-45% of the weight of glass-ceramic products.
19. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Spinel crystal phase accounts for 30-45% of the weight of glass-ceramic products.
20. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product having spinel crystal phase contains quartz crystal phase.
21. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product having spinel crystal phase contains quartz crystal phase, and the quartz crystal phase accounts for less than 20% of the weight of the microcrystalline glass product.
22. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product having spinel crystal phase contains quartz crystal phase, and the quartz crystal phase accounts for less than 10% of the weight of the microcrystalline glass product.
23. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product having spinel crystal phase contains quartz crystal phase, and the quartz crystal phase accounts for less than 5% of the weight of the microcrystalline glass product.
24. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product having spinel crystal phase does not contain quartz crystal phase.
25. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a percentage by weight, do not contain La2O3, and / or Gd2O3, and / or Yb2O3, and / or Nb2O5, and / or WO3, and / or Bi2O3, and / or Ta2O5, and / or TeO2.
26. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~5%.
27. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~2%.
28. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%.
29. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product has a grain size of less than 60 nm; and / or an ion exchange layer depth of more than 75 μm; and / or a surface stress of more than 200 MPa; and / or a drop ball test height of more than 1000 mm; and / or a drop resistance of more than 1200 mm; and / or a fracture toughness of 1.0 MPa·m. 1 / 2 The above; and / or a four-point flexural strength of 500 MPa or more; and / or a compressive strength of 400 N or more; and / or a Vickers hardness of 650 kgf / mm². 2 above.
30. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product has a grain size of less than 45 nm; and / or an ion exchange layer depth of 80–150 μm; and / or a surface stress of 250–400 MPa; and / or a drop ball test height of more than 1200 mm; and / or a drop resistance of more than 1300 mm; and / or a fracture toughness of 1.2 MPa·m. 1 / 2 The above; and / or a four-point flexural strength of 600 MPa or above; and / or a compressive strength of 400–550 N; and / or a Vickers hardness of 660 kgf / mm². 2 above.
31. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, The microcrystalline glass product has a grain size of 10–30 nm; and / or an ion exchange layer depth of 100–125 μm; and / or a surface stress of 300–400 MPa; and / or a drop ball test height of 1500 mm or more; and / or a drop resistance of 1400 mm or more; and / or a fracture toughness of 1.2–1.6 MPa·m. 1 / 2 ; and / or a four-point bending strength of 700–1000 MPa; and / or a compressive strength of 450–550 N; and / or a Vickers hardness of 680–750 kgf / mm². 2 .
32. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, For microcrystalline glass products with a thickness of less than 1 mm, the haze is less than 0.25%; and / or the average light transmittance at wavelengths of 400–800 nm is greater than 87.0%; and / or the light transmittance at wavelengths of 550 nm is greater than 87.0%; and / or the average light |B| value at wavelengths of 400–800 nm is 0.3–0.
6.
33. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, For microcrystalline glass products with a thickness of less than 1 mm, the haze is 0.05 to 0.2%; and / or the average light transmittance at wavelengths of 400 to 800 nm is 88.5% or more; and / or the light transmittance at wavelengths of 550 nm is 88.0% or more.
34. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, For microcrystalline glass products with a thickness of less than 1 mm, the average light transmittance at wavelengths of 400–800 nm is above 89.5%; and / or the light transmittance at wavelengths of 550 nm is above 89.0%.
35. The microcrystalline glass article having a spinel crystal phase according to claim 32, characterized in that, The thickness of the microcrystalline glass product is 0.2 to 1 mm.
36. The microcrystalline glass article having a spinel crystal phase according to claim 32, characterized in that, The thickness of the microcrystalline glass product is 0.3 to 0.9 mm.
37. The microcrystalline glass article having a spinel crystal phase according to claim 32, characterized in that, The thickness of the microcrystalline glass product is 0.5 to 0.8 mm.
38. The microcrystalline glass article having a spinel crystal phase according to claim 32, characterized in that, The thickness of the microcrystalline glass product is 0.55mm, 0.6mm, 0.68mm, 0.7mm, or 0.75mm.
39. The microcrystalline glass article having a spinel crystal phase according to any one of claims 1 to 4, characterized in that, Its components, expressed as a weight percentage, contain: NiO: 0–4%; and / or Ni₂O₃: 0–4%; and / or CoO: 0–2%; and / or Co₂O₃: 0–2%; and / or Fe₂O₃: 0–7%; and / or MnO₂: 0–4%; and / or Er₂O₃: 0–8%; and / or Nd₂O₃: 0–8%; and / or Cu₂O: 0–4%; and / or Pr₂O₃: 0–8%; and / or CeO₂: 0–4%.
40. A microcrystalline glass having a spinel crystal phase, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 41–55%; Al2O3+ZnO: 26–45%; Li2O: 0.1–6%; MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, of which Li2O / TiO2 is 0.4–4.5, Al2O3 / ZnO is 1.0–3.0, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass with a thickness of less than 1 mm is below 0.3%, and the average optical |B| value of 400–800 nm is below 0.
8.
41. The microcrystalline glass with spinel phase according to claim 40, characterized in that, Its components, expressed as a percentage by weight, also include: P2O5+ZrO2: 0–8%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Y2O3: 0–6%; and / or clarifying agent: 0–2%.
42. A microcrystalline glass having a spinel crystal phase, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 41–55%; Al2O3+ZnO: 26–45%; Li2O: 0.1–6%; MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, wherein Al2O3 / ZnO is 1.0–3.0, Li2O / TiO2 is 0.4–4.5, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass with a thickness of less than 1 mm is below 0.3%, the average light |B| value of 400–800 nm is below 0.8, and the light transmittance of microcrystalline glass with a thickness of less than 1 mm at a wavelength of 550 nm is above 87.0%.
43. A microcrystalline glass having a spinel crystal phase, characterized in that, The microcrystalline glass has a grain size of less than 60 nm, and its composition, expressed as a weight percentage, contains: SiO2: 41-55%; Al2O3+ZnO: 26-45%; Li2O: 0.1-6%. MgO: 0.1–6%; TiO2: 0.5–7%; Na2O: 0–4.9%; K2O: 0–3%, wherein Al2O3 / ZnO is 1.0–3.0, Li2O / TiO2 is 0.4–4.5, (Li2O+MgO) / TiO2 is 0.9–2.9, Al2O3 / (MgO+TiO2) is 1.8–10.0, (Na2O+K2O) / ZnO is below 0.45, the haze of microcrystalline glass with a thickness of less than 1 mm is below 0.3%, and the average optical |B| value of 400–800 nm is below 0.
8.
44. The microcrystalline glass with spinel phase according to claim 42 or 43, characterized in that, Its components, expressed as a percentage by weight, also include: P2O5+ZrO2: 0–8%; and / or B2O3: 0–4%; and / or CaO+BaO+SrO: 0–5%; and / or Y2O3: 0–6%; and / or clarifying agent: 0–2%.
45. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components are expressed as a weight percentage, wherein: Li2O / TiO2 is 0.5–3.5; and / or Al2O3 / ZnO is 1.2–2.8; and / or SiO2 / Al2O3 is 1.5–3.2; and / or (TiO2+ZnO) / Al2O3 is 0.4–1.5; and / or (Li2O+MgO) / TiO2 is 1.0–2.9; and / or Al2O3 / (MgO+TiO2) is 1.8–8.0; and / or (Al2O3+Li2O) / P2O5 is 5.0–45.0; and / or P2O5 / ZrO2 is 0.1–5.0; and / or (SiO2+Na2O) / ZnO is 2.2–6.2; and / or (Na2O+K2O) / ZnO is less than 0.
4.
46. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components are expressed as a weight percentage, wherein: Li2O / TiO2 is 0.7–2.5; and / or Al2O3 / ZnO is 1.5–2.5; and / or SiO2 / Al2O3 is 1.7–3.0; and / or (TiO2+ZnO) / Al2O3 is 0.5–1.2; and / or (Li2O+MgO) / TiO2 is 1.2–2.5; and / or Al2O3 / (MgO+TiO2) is 2.5–6.5; and / or (Al2O3+Li2O) / P2O5 is 7.0–35.0; and / or P2O5 / ZrO2 is 0.2–3.0; and / or (SiO2+Na2O) / ZnO is 2.5–6.0; and / or (Na2O+K2O) / ZnO is less than 0.
2.
47. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components are expressed as weight percentages, wherein: Li2O / TiO2 is 0.75–1.5; and / or Al2O3 / ZnO is 1.5–2.3; and / or SiO2 / Al2O3 is 1.8–2.8; and / or (TiO2+ZnO) / Al2O3 is 0.6–1.0; and / or Al2O3 / (MgO+TiO2) is 3.0–5.5; and / or (Al2O3+Li2O) / P2O5 is 8.0–30.0; and / or P2O5 / ZrO2 is 0.5–2.0; and / or (SiO2+Na2O) / ZnO is 2.8–5.
5.
48. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components are expressed as a weight percentage, wherein: SiO2 / Al2O3 is 2.0 to 2.5; and / or (TiO2+ZnO) / Al2O3 is 0.6 to 0.9; and / or (Al2O3+Li2O) / P2O5 is 10.0 to 25.0; and / or P2O5 / ZrO2 is 0.6 to 1.5; and / or (SiO2+Na2O) / ZnO is 3.0 to 5.
0.
49. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: SiO2: 45–53%; and / or Al2O3+ZnO: 30–42%; and / or Li2O: 1–5%; and / or MgO: 1–5%; and / or TiO2: 1–6%; and / or P2O5+ZrO2: 0.1–7%; and / or Na2O: 0–4%; and / or B2O3: 0–2%; and / or K2O: 0–2%; and / or CaO+BaO+SrO: 0–4%; and / or Y2O3: 0–4%; and / or clarifying agent: 0–1%.
50. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: SiO2: 48–52%; and / or Al2O3+ZnO: 32–42%; and / or Li2O: 2–4%; and / or MgO: 2–4%; and / or TiO2: 2–5%; and / or P2O5+ZrO2: 0.5–5%; and / or Na2O: 0–2%; and / or B2O3: 0–1%; and / or K2O: 0–1%; and / or CaO+BaO+SrO: 0–2%; and / or Y2O3: 0–2%; and / or clarifying agent: 0–0.5%.
51. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its composition, expressed as a percentage by weight, contains: Al2O3 + ZnO: 35-40%.
52. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 15-30%; and / or ZnO: 9-20%; and / or P2O5: 0-5%; and / or ZrO2: 0-5%.
53. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 18–25%; and / or ZnO: 11–18%; and / or P2O5: 0.5–4%; and / or ZrO2: 0.5–4%.
54. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a percentage by weight, contain: Al2O3: 20–23%; and / or ZnO: 12–16%; and / or P2O5: 1–3%; and / or ZrO2: 1–3%.
55. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Spinel crystal phase accounts for 20-60% of the weight of glass-ceramics.
56. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The spinel phase accounts for 25-50% of the weight of the glass-ceramic.
57. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The spinel phase accounts for 25-45% of the weight of the glass-ceramic.
58. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The spinel phase accounts for 30-45% of the weight of the glass-ceramic.
59. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass with spinel phase contains quartz phase.
60. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass with spinel phase contains quartz phase, and the quartz phase accounts for less than 20% of the weight of the microcrystalline glass.
61. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass with spinel phase contains quartz phase, and the quartz phase accounts for less than 10% of the weight of the microcrystalline glass.
62. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass with spinel phase contains quartz phase, and the quartz phase accounts for less than 5% of the weight of the microcrystalline glass.
63. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass with spinel phase does not contain quartz phase.
64. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a percentage by weight, do not contain La2O3, and / or Gd2O3, and / or Yb2O3, and / or Nb2O5, and / or WO3, and / or Bi2O3, and / or Ta2O5, and / or TeO2.
65. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~5%.
66. The glass-ceramic having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~2%.
67. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: La2O3+Gd2O3+Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2: 0~1%.
68. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass has a grain size of less than 60 nm; and / or a Young's modulus of 80–110 GPa; and / or a Vickers hardness of 550 kgf / mm². 2 above.
69. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass has a grain size of less than 45 nm; and / or a Young's modulus of 85–105 GPa; and / or a Vickers hardness of 580 kgf / mm. 2 above.
70. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The microcrystalline glass has a grain size of 10–30 nm; and / or a Young's modulus of 90–105 GPa; and / or a Vickers hardness of 600–650 kgf / mm². 2 .
71. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The haze of microcrystalline glass with a thickness of less than 1 mm is less than 0.25%; and / or the average light transmittance at wavelengths of 400 to 800 nm is greater than 87.0%; and / or the light transmittance at wavelengths of 550 nm is greater than 87.0%; and / or the average light |B| value at wavelengths of 400 to 800 nm is 0.3 to 0.
6.
72. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The haze of microcrystalline glass with a thickness of less than 1 mm is 0.05 to 0.2%; and / or the average light transmittance at wavelengths of 400 to 800 nm is 88.5% or more; and / or the light transmittance at wavelengths of 550 nm is 88.0% or more.
73. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, The average light transmittance of microcrystalline glass with a thickness of less than 1 mm at wavelengths of 400–800 nm is above 89.5%; and / or the light transmittance at wavelength of 550 nm is above 89.0%.
74. The microcrystalline glass with spinel phase according to claim 71, characterized in that, The thickness of the microcrystalline glass is 0.2 to 1 mm.
75. The microcrystalline glass with spinel phase according to claim 71, characterized in that, The thickness of the microcrystalline glass is 0.3 to 0.9 mm.
76. The microcrystalline glass with spinel phase according to claim 71, characterized in that, The thickness of the microcrystalline glass is 0.5 to 0.8 mm.
77. The microcrystalline glass with spinel phase according to claim 71, characterized in that, The thickness of the microcrystalline glass is 0.55mm, 0.6mm, 0.68mm, 0.7mm, or 0.75mm.
78. The microcrystalline glass having a spinel phase according to any one of claims 40 to 43, characterized in that, Its components, expressed as a weight percentage, contain: NiO: 0–4%; and / or Ni₂O₃: 0–4%; and / or CoO: 0–2%; and / or Co₂O₃: 0–2%; and / or Fe₂O₃: 0–7%; and / or MnO₂: 0–4%; and / or Er₂O₃: 0–8%; and / or Nd₂O₃: 0–8%; and / or Cu₂O: 0–4%; and / or Pr₂O₃: 0–8%; and / or CeO₂: 0–4%.
79. A glass cover plate, characterized in that, The microcrystalline glass article containing the spinel crystal phase as described in any one of claims 1 to 39, and / or the microcrystalline glass containing the spinel crystal phase as described in any one of claims 40 to 78.
80. A glass component, characterized in that, The microcrystalline glass article containing the spinel crystal phase as described in any one of claims 1 to 39, and / or the microcrystalline glass containing the spinel crystal phase as described in any one of claims 40 to 78.
81. An electronic device, characterized in that, The microcrystalline glass article containing the spinel crystal phase as described in any one of claims 1 to 39, and / or the microcrystalline glass containing the spinel crystal phase as described in any one of claims 40 to 78, and / or the glass cover plate as described in claim 79, and / or the glass component as described in claim 80.
82. A display device, characterized in that, The microcrystalline glass article containing the spinel crystal phase as described in any one of claims 1 to 39, and / or the microcrystalline glass containing the spinel crystal phase as described in any one of claims 40 to 78, and / or the glass cover plate as described in claim 79, and / or the glass component as described in claim 80.
83. A method for manufacturing a microcrystalline glass article having a spinel crystal phase as described in any one of claims 1 to 39, characterized in that, The method includes the following steps: forming a matrix glass, crystallizing the matrix glass to form a microcrystalline glass with a spinel crystal phase, and then chemically strengthening the microcrystalline glass with a spinel crystal phase to form a microcrystalline glass product with a spinel crystal phase.
84. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The formation of the matrix glass includes the following steps: The raw materials are mixed evenly according to the component ratio, and then placed in a crucible. The mixture is melted in an electric furnace or gas furnace at a temperature range of 1350-1550℃ for 5-24 hours. After clarification, homogenization, shaping, and annealing, the matrix glass is obtained. The clarification temperature is greater than 1550℃ but less than or equal to 1650℃, and the annealing temperature is 450-600℃.
85. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The formation of the matrix glass includes the following steps: The raw materials are mixed evenly according to the component ratio, and then placed in a crucible. The mixture is melted in an electric furnace or gas furnace at a temperature range of 1450-1550℃ for 5-24 hours. After clarification, homogenization, shaping, and annealing, the matrix glass is obtained. The clarification temperature is greater than 1550℃ but less than or equal to 1650℃, and the annealing temperature is 450-600℃.
86. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The crystallization process includes the following steps: heating to a specified crystallization temperature, maintaining the temperature for a certain period of time after reaching the crystallization temperature, and then cooling down. The crystallization temperature is 600-800℃, and the holding time at the crystallization temperature is 1-10 hours.
87. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The crystallization process includes the following steps: heating to a specified crystallization temperature, maintaining the temperature for a certain period of time after reaching the crystallization temperature, and then cooling down. The crystallization temperature is 650-750°C, and the holding time at the crystallization temperature is 3-6 hours.
88. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature. The first temperature is 600-700°C, and the second temperature is greater than 700°C but less than or equal to 800°C. The holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
89. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The chemical strengthening process includes: immersing microcrystalline glass with a spinel crystal phase in a salt bath of molten Na salt at 350–470°C for 1–36 hours; and / or immersing microcrystalline glass with a spinel crystal phase in a mixed salt bath of molten K salt and Na salt at 360–450°C for 1–36 hours.
90. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 83, characterized in that, The chemical strengthening process includes: immersing microcrystalline glass with a spinel crystal phase in a salt bath of molten Na salt at 400–460°C for 2–15 hours; and / or immersing microcrystalline glass with a spinel crystal phase in a mixed salt bath of molten K salt and Na salt at 360–450°C for 2–24 hours.
91. A method for manufacturing a microcrystalline glass having a spinel phase according to any one of claims 40 to 78, characterized in that, The method includes the following steps: forming a matrix glass, and then using a crystallization process to form a microcrystalline glass with a spinel crystal phase.
92. The method for manufacturing a microcrystalline glass with a spinel phase according to claim 91, characterized in that, The formation of the matrix glass includes the following steps: The raw materials are mixed evenly according to the component ratio, and then placed in a crucible. The mixture is melted in an electric furnace or gas furnace at a temperature range of 1350-1550℃ for 5-24 hours. After clarification, homogenization, shaping, and annealing, the matrix glass is obtained. The clarification temperature is greater than 1550℃ but less than or equal to 1650℃, and the annealing temperature is 450-600℃.
93. The method for manufacturing microcrystalline glass with a spinel crystal phase according to claim 91, characterized in that, The formation of the matrix glass includes the following steps: The raw materials are mixed evenly according to the component ratio, and then placed in a crucible. The mixture is melted in an electric furnace or gas furnace at a temperature range of 1450-1550℃ for 5-24 hours. After clarification, homogenization, shaping, and annealing, the matrix glass is obtained. The clarification temperature is greater than 1550℃ but less than or equal to 1650℃, and the annealing temperature is 450-600℃.
94. The method for manufacturing a microcrystalline glass with a spinel phase according to claim 91, characterized in that, The crystallization process includes the following steps: heating to a specified crystallization temperature, maintaining the temperature for a certain period of time after reaching the crystallization temperature, and then cooling down. The crystallization temperature is 600-800℃, and the holding time at the crystallization temperature is 1-10 hours.
95. The method for manufacturing a microcrystalline glass with a spinel phase according to claim 91, characterized in that, The crystallization process includes the following steps: heating to a specified crystallization temperature, maintaining the temperature for a certain period of time after reaching the crystallization temperature, and then cooling down. The crystallization temperature is 650-750°C, and the holding time at the crystallization temperature is 3-6 hours.
96. The method for manufacturing a microcrystalline glass article having a spinel crystal phase according to claim 91, characterized in that, The crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature. The first temperature is 600-700°C, and the second temperature is greater than 700°C but less than or equal to 800°C. The holding time at the first temperature is 1-6 hours, and the holding time at the second temperature is 2-5 hours.
Citation Information
Patent Citations
Crystallized glass substrate for information recording medium and method of producing the same
CN101905952A
Glass ceramic, glass ceramic product and manufacturing method thereof
CN114907014A
Tempered glass, microcrystalline glass and preparation method and application thereof
CN115286251A